C.A. Larsen - Pioneer of the Antarctic ocean - Devig, Thor N (Norwegian maritime explorers and expeditions : over the past thousand years, 1999)
Keywords: Antarktis; Carl Anton Larsen; Nordmenn; Sørishavet; historie; hvalfangst; kartlegging; oppdagelsesreiser; pelagisk; polarekspedisjoner

Functional biodiversity of lipids in Antarctic zooplankton: Calanoides acutus, Calanus propinquus, Thysanoessa macrura and Euphausia crystallorophias - Falk-Petersen, Stig; Sargent, John R; Lønne, Ole Jørgen; Timofeev, Sergej (Polar Biology, 1999)
Zooplankton samples were collected in January 1993 off Dronning Maud Land along a transect from open waters to the marginal ice zone close to the Antarctic ice shelf. Thysanoessa macrura was caught in open waters while Calanoides acutus and Calanus propinquus were mainly sampled between ice floes in the marginal ice zone. The “ice-krill”Euphausia crystallorophias was found over the shelf directly associated with ice floes. T. macrura had a lipid content up to 36% of its dry weight with the dominant lipid class, wax ester, accounting for 45–50% of the total lipid. The predominance of 18:1 fatty alcohols is the striking characteristic of the wax esters. Small specimens of E. crystallorophias had lipid levels up to 26% of their dry weight with, unexpectedly, triacylglycerols being the dominant lipid (up to 41% of total lipid). The small levels of wax esters in these animals (3–6% of total lipid) had phytol as a major constituent. Large specimens of E. crystallorophias had up to 34% of their dry weight as lipid, with wax esters (47% of total lipid) dominated by 16:0 and 14:0 fatty alcohols as the major lipid. Calanus propinquus had lipid levels of up to 34% of their dry weight, with triacylglycerols (up to 63% of total lipid) being the dominant lipid. High levels of 22:1 (n-9) fatty acid were present in the triacylglycerols. Calanoides acutus had lipid levels up to 35% of the dry weight with wax esters accounting for up to 83% of total lipid. High levels of (n-3) polyunsaturated fatty acids were recorded with 20:5(n-3), 22:6(n-3) and 18:4(n-3) being the dominant moieties. On the basis of their lipid compositions we deduce that: (1) Calanoides acutus is the strictest herbivore among the four species studied, heavily utilizing the typical spring bloom; (2) T. macrura is essentially omnivorous, probably utilizing the less defined bloom situations found in oceanic waters; (3) E. crystallorophias is an omnivore well adapted to utilize both a bloom situation and to feed on ice algae and micro-zooplankton associated with the ice; (4) Calanus propinquus seems to be the most opportunistic feeder of the four species studied, probably grazing heavily on phytoplankton during a bloom and, during the rest of the year, feeding on whatever material is available, including particulates, flagellates and other ice-associated algae. We conclude that the different biochemical pathways generating large oil reserves of different compositions, enabling species to utilize different ecological niches, are major determinants of biodiversity in polar zooplankton.
Keywords: NARE 1992/93; Sørishavet; biodiversitet; biokjemi; dyreplankton; krill; lipider; marin biologi; zooplankton

In search of an elusive Antarctic circumpolar wave in sea ice extents: 1978–1996 - Gloersen, Per; Huang, Norden E. (Polar Research, 1999)
For ease in discerning an Antarctic circumpolar wave in the perimeter of the ice pack, we construct a time series of the sea ice extents (essentially the area within the ice perimeter) in 1-degree longitudinal sectors for the period 1978-1996, as observed with the multichannel microwave imagers on board the NASA Nimbus 7 and the DOD (Dept. of Defense) DMSP (Defense Meteorological Satellite Program) F8, F11, and F13 satellites. After converting the time series into complex numbers by means of a Hilbert transform, we decompose the time series of the 360 sectors into its complex principal components (CPCs), effectively separating the spatial and temporal values. Then we decompose the real and imaginary parts of the temporal portions of the first three CPCs (complex principal compenents) by Empirical Mode Decomposition into their intrinsic modes, each representing a narrow frequency band, resulting in a collection of three CPCs for each intrinsic mode. Finally, we reconstruct the data in two different ways. First, we low-pass filter the data by combining all of the intrinsic modes of each CPC with periods longer than two years, which we designate as lowpass filtered. Next, we select the intrinsic mode of each CPC with periods of approximately four years, which we designate the quasiquadrennial (QQ) modes. The low-pass filtered time series shows eastward propagating azimuthal motion in the Ross and Weddell Seas, but no clearly circumpolar motion. The QQ time series, on the other hand, clearly shows eastward propagating circumpolar waves, but with occasional retrograde motion to the west.
Keywords: Rosshavet; Sørishavet; Weddellhavet; havis; klimatologi; meteorologi; oseanografi

Physical oceanography - Nøst, Ole Anders; Enghum, Elisabeth; Djurfeldt, Leif; Larsson, Anne-Marie (Report of the Norwegian Antarctic Research Expedition 1997/98, 1999)
Keywords: NARE 1997/98; Sørishavet; fysisk oseanografi

Iron enrichment with hydrocarboxylic acid and photoreduction of iron under UV and PAR: implications for phytoplankton growth in the Antarctic Ocean. Some preliminary results - Öztürk, Murat; Sakshaug, Egil (Report of the Norwegian Antarctic Research Expedition 1997/98, 1999)
Keywords: NARE 1997/98; Sørishavet; fytoplankton; marin biologi; oseanografi

Residue determinants and sequence analysis of cold-adapted trypsins - Schrøder Leiros, Hanna-Kirsti; Willassen, Nils Peder; Smalås, Arne O. (Extremophiles, 1999)
The digestive enzyme trypsin is among the most extensively studied proteins, and its structure has been reported from a large number of organisms. This article focuses on the trypsins from vertebrates adapted to life at low temperatures. Cold-adapted organisms seem to have compensated for the reduced reaction rates at low temperatures by evolving more active and less temperature-stable enzymes. We have analyzed 27 trypsin sequences from a variety of organisms to find unique attributes for the cold-adapted trypsins, comparing trypsins from salmon, Antarctic fish, cod, and pufferfish to other vertebrate trypsins. Both the "cold" and the "warm" active trypsins have about 50 amino acids that are unique and conserved within each class. The main unique features of the cold-adapted trypsins attributable to low-temperature adaptation seem to be (1) reduced hydrophobicity and packing density of the core, mainly because of a lower (Ile + Leu)/(Ile + Leu + Val) ratio, (2) reduced stability of the C-terminal, (3) lack of one warm trypsin conserved proline residue and one proline tyrosine stacking, (4) difference in charge and flexibility of loops extending the binding pocket, and (5) different conformation of the "autolysis" loop that is likely to be involved in substrate binding.
Keywords: Sørishavet; biokjemi; fisker; marin biologi; mikrobiologi; polarområdene

Forskrift om regulering av fiske med norske fartøyer i Antarktis (CCAMLR-området) - fiskeridepartementet, Nærings- og (Lovdata, 1998)
Keywords: Sørishavet; fiskeri; jus

Research cruise of the Scandinavian South African Antarctic expedition, December 1997 to February 1998 - Froneman, P.W.; Pakhomov, Evgeny; Turner, D.; Abrahamson, K.; Karlsson, B.; Godhe, Anna; Bertilsson, Stefan; Graneli, Wilhelm; Carlsson, Per; Wängberg, Sten-Åke; Wulff, Angela; Croot, Peter; et al. (South African Journal of Science, 1998)
Focuses on the Scandinavian/South African Antarctic expedition conducted between December 4, 1997 to February 6, 1998 which determined the role of Southern Ocean in the global carbon cycle in physical and biological oceanographic studies. Aims of the expedition; Underway sampling conducted; Biological results of the expedition; Conclusions.
Keywords: NARE ekspedisjoner; Sørishavet; fytoplankton; krill; marin biologi; oseanografi

Norway and the polar regions - Hansson, Rasmus (The Royal Norwegian Ministry of Foreign Affairs, 1998)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

Nitrogen uptake in the infiltration community, an ice algal community in Antarctic pack-ice - Kristiansen, Svein; Farbrot, Tove; Kuosa, Harri; Myklestad, Sverre M; Quillfeldt von, Cecilie Hellum (Polar Biology, 1998)
An infiltration community was the dominating ice algal community in pack-ice off Queen Maud Land, Southern Ocean, in January 1993. The community was dominated by autotrophic processes, and the most common species were the prymnesiophyte Phaeocystis antarctica and the diatoms Chaetoceros neglectus and Fragilariopsis cylindrus. The concentration of chlorophyll a was 1.3–47.9 μg l−1, and the inner part of the community was nitrate depleted. Uptake rates of nitrate, nitrite, ammonium, urea and amino acids were measured using 15N. Nitrate was the major nitrogen source for ice algal growth (67 ± 6% nitrate uptake). It is suggested that % nitrate uptake in the infiltration community decreases during the growth season, from 92% during spring (literature data) to 67% during summer. Scalar irradiance in the infiltration community was high and variable. It reached ca. 2000 μmol m−2 s−1 at some locations, and nitrate uptake rate was potentially photoinhibited at irradiances >500 μmol m−2 s−1. Nitrate uptake rate in an average infiltration community (0.6 m of snow cover) was lowered by 13% over a 2-week period due to photoinhibition.
Keywords: Sørishavet; Weddellhavet; alger; marin biologi

Establishing chronologies from acid-insoluble organic 14C dates on Antarctic (Ross Sea) and Arctic (North Atlantic) marine sediments - Licht, Kathy J; Cunningham, Wendy L; Andrews, John T; Domack, Eugene W; Jennings, Anne E (Polar Research, 1998)
Keywords: Rosshavet; Sørishavet; paleoseanografi; polarområdene; sedimentologi

Gut length, food transit time and diving habit in phocid seals - Mårtensson, Per-Erik; Nordøy, Erling; Messelt, Edward; Blix, Arnoldus Schytte (Polar Biology, 1998)
Keywords: Sørishavet; seler; zoologi

Snipp snapp snute... : beretning om livet om bord i hvalbåtene fra Vestfold på fangstfeltene i Sydishavet - Østevik, Tore (Færder forlag, 1998)
Keywords: Norge; Sørishavet; historie; hvalfangere; hvalfangst; pelagisk; sjøfolk

Stability of the Thermohaline Circulation to Noisy Surface Buoyancy Forcing for the Present and a Warm Climate in an Ocean General Circulation Model - Skagseth, Øystein; Mork, Kjell Arne (Journal of Physical Oceanography, 1998)
The stabilities of two different circulation regimes in the North Atlantic, 1) the present thermohaline circulation and 2) a weaker thermohaline circulation, are compared using the Hamburg Large Scale Geostrophic (LSG) ocean circulation model. The latter circulation regime is obtained by restoring the LSG model toward an on average 48C warmer air surface temperature corresponding to a doubled atmospheric content of CO 2 . The stabilities of these stationary states are investigated by imposing various amounts of stochastic noise on the surface freshwater flux. The simulations show more variability on secular timescales for the present than for the warm climate. Since the modeled static stabilities for the two climates are relatively similar, the different rates of variability are probably connected to other mechanisms. In the present climate at high latitudes the two buoyancy fluxes due to heat and freshwater are of similar magnitudes but with opposite signs; thus switches between convective and nonconvective periods at secular timescales are possible. In the warm climate the buoyancy flux due to heat dominates. This compensates the effect of the noisy freshwater forcing and thus reduces the potential for secular oscillations. The stronger coupling between the Atlantic and the Southern Ocean for the present relative to the warm climate could also contribute to this difference. Furthermore, the simulations show that the variability of the Antarctic Circumpolar Current transport for the present climate exceeds that of the warm climate. For increasing stochastic noise the present circulation approaches that of the warm circulation. The authors apply a mixture of heat flux and temperature restoring for the surface boundary condition. Comparison with similar works, which apply a pure restoring for surface temperature, shows that the ocean circulation is much less sensitive to forced stochastic freshwater anomalies with the type of boundary condition used herein. A box model is used to illustrate the effects of the surface temperature parameterizations and the different buoyancy forcing for the present and warm climate.
Keywords: AABW; Sørishavet; Sørishavsstrømmen; geofysikk; havstrømmer; oseanografi; polarområdene; vannmasser

Experimental formation of sea ice: importance of water circulation and wave action for incorporation of phytoplankton and bacteria - Weissenberger, Jürgen; Grossmann, Sönnke (Polar Biology, 1998)
The efficiency of physical concentration mechanisms for enrichment of algae and bacteria in newly formed sea-ice was investigated under defined conditions in the laboratory. Sea-ice formation was simulated in a 3,000 l tank under different patterns of water movement. When ice formed in an artificially generated current pattern, algal cells were substantially enriched within the ice matrix. Enrichment factors for chlorophyll a calculated from the ratio between the concentrations in ice and underlying water reached values of up to 53. Repeated mixing of ice crystals into the water column, as well as flow of water through the new ice layer, contributed to the enrichment of algae in the ice. Wave action during ice formation revealed lower phytoplankton enrichment factors of up to 9. Mixing of floating ice crystals with underlying water and pumping of water into the ice matrix by periodical expansion and compression of the slush ice layer were responsible for the wave-induced enrichment of algal cells. Physical enrichment of bacteria within the ice was negligible. Bacterial biomass within new ice was enhanced only when the concentration of algae was high. At low algal biomass, bacteria experienced substantial losses in the ice, most likely due to brine drainage, which were not observed for the microalgae. Bacterial cells are therefore not scavenged by ice crystals and the observed enrichment and sustainment of bacterial biomass within newly formed ice depend on their attachment to cells or aggregates of algae. Division rates of bacteria changed only slightly during ice formation.
Keywords: Sørishavet; Weddellhavet; alger; bakterier; fytoplankton; havis; marin biologi; polarområdene

Døde menn vender tilbake: Shackletons høyst private Whitbread-seilas - Winge, Jon (Norsk sjøfartsmuseum. Årbok, 1998)
Keywords: Endurance (skip); Ernest Henry Shackleton; Sørishavet; ekspedisjoner; oppdagelsesreiser; skipsfart

Chemical composition in water masses and interactions with the sediment in the southern Weddel sea - Anderson, Leif G; Fogelqvist, Elisabet; Hulth, Stefan; Olsson, Kristina; Tanhua, Toste; Tengberg, Anders; Zemlyak, Frank (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: NARE 1992/93; Sørishavet; Weddellhavet; analyser; kjemisk; sedimenter; vannmasser

Productivity in the 20th century Antarctic pelagic shore station whaling: growth and stagnation in two technological regimes. - Basberg, Bjørn L (The Great Circle, 1997)
Keywords: Antarktis; Sørishavet; historie; hvalfangstindustri; hvalfangststasjoner; hvalindustri; pelagisk

To hvalfangstentreprenøren - to strategier? - Basberg, Bjørn L (I det lange løp : essays i økonomisk historie tilegnet Fritz Hodne, 1997)
Keywords: Antarktis; Carl Anton Larsen; Christen Christensen; Norge; Sørishavet; historie; hvalfangstindustri; hvalfangstselskaper; hvalfangststasjoner; hvalkokerier; næringsliv; pelagisk; økonomi

Water masses in the southern Weddell Sea - Gammelsrød, Tor; Myking, Steinar; Nøst, Anders; Skagseth, Øystein; Østerhus, Svein (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: NARE 1992/93; Sørishavet; Weddellhavet; innlandsis; oseanografi; vannmasser

Productivity in the southern Weddell Sea in the Austral summer - Hegseth, Else Nøst; Quillfeldt von, Cecilie Hellum; Seim, Bjørnar (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: NARE 1996/97; Sørishavet; alger; fytoplankton; krill

Timing of glacial events in Antarctica - diamond drilling into the glaciomarine sequence of the Weddell Sea continental shelf - Koç, Nalân; Kuvaas, Berit; Kristoffersen, Yngve; Hansen, Erik; Persson, Allan (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: NARE 1996/97; Sørishavet; Weddellhavet; glasiologi; kontinentalsokkel; sedimenter; sedimentologi; seismologi

Ice algae and phytoplankton composition in the Weddell Sea: interactions, production and nitrogen uptake - Kristiansen, Svein; Syvertsen, Erik E.; Farbrot, Tove (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: NARE 1992/93; Sørishavet; Weddellhavet; alger; fytoplankton

Sea ice projects during NARE 1992/93 - Løyning, Terje Brinck; Vinje, Torgny (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: NARE 1992/93; Sørishavet; Weddellhavet; havis; sjøis

Hval og hvalfangst : temahefte - [Lunde, Stig-Tore] (Sandefjordmuseene, 1997)
Keywords: Sørishavet; historie; hvalfangere; hvalfangstindustri; hvalindustri; pelagisk

Studies of seals in the Weddel sea and King Haakon VII sea - Nordøy, Erling S; Blix, Arnoldus Schytte (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: NARE 1996/97; Sørishavet; Weddellhavet; seler; zoologi

The Antarctic coastal current - physical oceanographic results from NARE 1996/97 - Nøst, Ole Anders; Lothe, Torleif (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: NARE 1996/97; Sørishavet; oseanografi

Sandefjords historie - Olstad, Finn (Sandefjord kommune, 1997)
Keywords: Nordmenn; Norge; Sørishavet; Vestfold; historie; hvalfangere; hvalfangst; hvalfangstindustri; hvalindustri

Ice algae and phytoplankton composition in the Weddell Sea: interactions with different environmental factors - Quillfeldt von, Cecilie Hellum (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: NARE 1992/93; Sørishavet; Weddellhavet; alger; fytoplankton

Lack of population subdivision among the minke whales (Balaenoptera acutorostrata) from Icelandic and Norwegian waters based on mitochondrial DNA sequences - Bakke, Ingrid; Johansen, Steinar; Bakke, [Øyvind]; El-Gewely, Mohamed Raafat (Marine Biology, 1996)
The minke whale (Balaenoptera acutorostrata) is subject to commercial whaling, but stock identification and assessment are still uncertain. Mitochondrial DNA (mtDNA) sequences were determined to examine the population structure of minke whales from the central and northeastern parts of the North Atlantic, as well as the Antarctic regions IV and V. The analyses include 345 nucleotide positions of the control region of 110 individuals, and 250 nucleotide positions of the NADH dehydrogenase subunit 2 gene for a representative selection of North Atlantic minke whales. Maximum parsimony analyses and sequence divergence calculations did not reveal any genetic differentiation between individuals from the central and northeastern parts of the North Atlantic. These results do not support the International Whaling Commission's separation of minke whales in this area into different management units, and they are in conflict with previously reported results from allozyme analyses. Comparison of minke whale control region sequences showed that the sequence diversity of North Atlantic minke whales is substantially lower (0.0065) than that of Antarctic minke whales (0.0166), and clearly demonstrated that individuals from these two areas represent genetically distinct populations.
Keywords: Sørishavet; bioteknologi; genetikk; hvaler; marin biologi; polarområdene

Antarctic krill Thysanoessa macrura fills a major gap in marine lipogenic pathways - Kattner, Gerhard; Hagen, Wilhelm; Falk-Petersen, Stig; Sargent, John R.; Henderson R. James (Marine Ecology Progress Series, 1996)
The unique predominance of oleyl alcohols (18:1) is the striking characteristic of the lipids of the Antarctic euphausiid Thysanoessa macrura. The 2 isomers 18:1(n-9) and 18:1(n-7) occurred in similar proportions in the wax esters of T. macrura and comprised up to 80% of the total fatty alcohols. The remainder consisted mostly of the 20:1(n-9) alcohol along with small amounts of the 22:1(n-11) alcohol. No marine zooplankton species has previously been reported which produces wax esters with significant amounts of 18 carbon fatty alcohols. T. macrura specimens were collected in the high Antarctic Weddell Sea during autumn 1992 and summer 1993. Their lipid levels were high, about 40 to 50% of the dry mass with up to 70% of the total lipid as wax esters. The wax ester fatty acids were dominated by the saturates 14:0 and 16:0, which, along with the monounsaturate 18:1(n-9), accounted for more than 80% of the total fatty acids. Phospholipids contained high levels of (n-3) polyunsaturated fatty acids (20:5 and 22:6) typical of membrane lipids from marine zooplankton. The precise significance of the unique wax ester composition in T. macrura is not clear but this discovery underscores the biochemical adaptability of Antarctic zooplankton species to a constantly cold and highly seasonal polar environment.
Keywords: Sørishavet; Weddellhavet; biokjemi; dyreplankton; hoppekreps; krill; marin biologi; zooplankton; økologi

Modelling the ocean response to secular surface temperature transitions - Mork, K. A.; Skagseth, Øystein (Climate Dynamics, 1996)
The ocean response to surface temperature transients is simulated with the use of the Hamburg large-scale geostrophic (LSG) ocean general circulation model (OGCM). The transition, from the present to a climate corresponding to a doubling of the atmospheric CO2 content, is compared with the reversed transition. For the Atlantic, the time scale for the deep ocean to adjust to the temperature changes was similar for both transitions. In the Pacific, the time scale is shorter for the present to warm transition than for the reverse case, a result of increased production of Antarctic bottom water (AABW) during the warm climate. While the transition from cold to warm climate shows no secular variability, the reversed transition generates considerable variability on time scales of 300–400 years. For the warm climate, oscillations with periods of 45 years are found in the Southern Ocean. Results of principal oscillation pattern (POP) analysis indicate that these oscillations are due to interaction between convection in the Southern Ocean and advected salinity anomalies in the Antarctic Circumpolar Current (ACC) and the Southern Pacific Ocean.
Keywords: AABW; Sørishavet; Sørishavsstrømmen; geofysikk; havstrømmer; oseanografi; vannmasser

Effects of UV radiation on post-bloom phytoplankton populations in Kvalsund, North Norway - Walter Helbling, E.; Eilertsen, Hans Chr.; Villafañe, Virginia E.; Holm-Hansen, Osmund (Journal of Photochemistry and Photobiology B: Biology, 1996)
Our studies in the coastal waters in North Norway show that rates of photosynthesis of natural phytoplankton assemblages are strongly inhibited by solar UV radiation. When exposed to high irradiances of direct solar radiation, photosynthetic rates were increased by approximately 150% when all UV radiation was excluded from samples, with UVB radiation being responsible for approximately 50% of the total inhibition. There was no discernible threshold value for inhibition of photosynthesis by UV radiation, even at UV (280–400 nm) irradiances as low as 0.1 W m−2. When natural assemblages were incubated in situ, inhibition of photosynthetic rates were detectable down to 10 m, where solar irradiance was about 3% of the radiation incident on the sea surface. Based on the inhibition of photosynthetic rates at very low fluences of UV radiation, post-bloom assemblages of phytoplankton in North Norway and possibly also in the Arctic ocean appear to be more sensitive to solar UV radiation than phytoplankton from the Southern Ocean.
Keywords: Sørishavet; fotosyntese; fytoplankton; marin biologi; polarområdene; ultrafiolett stråling

Hvalen – ressurs og politikk – Historisk overblikk - Fløistad, Brit (Vestfoldminne, 1995)
Keywords: Sørishavet; historie; hvalfangere; hvalfangst; pelagisk

Distribution and diving behaviour of crabeater seals (Lobodon carcinophagus) off Queen Maud Land - Nordøy, Erling S.; Folkow, Lars; Blix, Arnoldus Schytte (Polar Biology, 1995)
Eight crabeater seals (Lobodon carcinophagus) (three females, five males), ranging in body mass between 125 and 220 kg, were captured off Queen Maud Land (70-72 degrees S, 7-16 degrees W) during the last week of February, just after moulting, and tagged with Argos satellite-linked dive recorders to provide data on location and diving depth and duration. During the first few weeks of March the seals were moving in the pack ice along the continental shelf edge, close to the coast of Queen Maud Land. In April and May, when the pack ice extended northwards, most of the seals moved north, one reaching 63 degrees S in late May. In the first half of June the two remaining seals turned south and moved back deep into the pack ice. The seals made about 150 dives per day each throughout the study period. Ninety percent of these were made to depths of less than 52 m. Individual maximum diving depths varied between 288 and 528 m. In March the seals were most active at night, when the dive depth was shallower than during the day. In April and May the seals were more active during day-time, with an absence of any diurnal change in diving depth. These results support the notion that crabeater seals predominantly feed on krill in Antarctic pack ice, even when winter returns to the waters off Queen Maud Land.
Keywords: Dronning Maud Land; Sørishavet; Weddellhavet; biodiversitet; marin biologi; seler; telemetri; zoologi; økologi

Åpning av Foyn-seminaret 23.januar 1995 - Olsen, Jan Henry T (Vestfoldminne, 1995)
Keywords: Den internasjonale hvalfangstkommisjonen; Norge; Svend Foyn; Sørishavet; historie; hvalfangere; hvalfangst; hvalfangstkvotene; pelagisk

Variability in nutrient concentrations around Elephant Island, Antarctica, during 1991-1993 - Silva S, Nelson; Helbling, E Walter; Villafañe, Virginia; Amos, Anthony F; Holm-Hansen, Osmund (Polar Research, 1995)
Keywords: Elefantøya; Sørishavet; næringsstoffer; vannmasser

Modelling of Deep-Sea Gravity Currents Using an Integrated Plume Model - Alendal, Guttorm; Drange, Helge; Haugan, Peter M (The Polar Oceans and Their Role in Shaping the Global Environment, 1994)
An integrated plume model is used to describe large scale gravity currents in the ocean. The model describes competing effects of (negative) buoyancy, friction, entrainment and Cariolis farce, as well as a pressure term due to variable plume thickness, on the flux, speed and flow direction of the plume. Equations for conservation of salt and internal energy (temperature) and a full equation of state far seawater is included in the model. The entrainment of ambient water is parameterized with support in empirical data, and a drag coefficient consistent with the entrainment is introduced. The model is tested against the overflow through the Denmark Strait, the flow down the Weddell Sea continental slope, and the outflow of saline water through the Gibraltar Strait and from the Spencer Gulf, Australia. The farmer gain an extra driving mechanism due to the thermobaric effect, while in the two latter cases the initial density difference is so large that this effect is not essential. Order of magnitude fit with measurements requires drag coefficient between 0.01 and 0.1. Conditions susceptible to meander behaviour and a singularity arising from the pressure dependency on the current thickness variations are briefly discussed.
Keywords: Sørishavet; Weddellhavet; havbunnen; havstrømmer; klimamodeller; oseanografi

Antarktis: verdens siste villmark - Fothergill, Alastair (Cappelen, 1994)
Keywords: Antarktis; Sørishavet; biologi; natur

Synedropsis gen. nov., a genus of araphid diatoms associated with sea ice - Hasle, Grethe Rytter; Medlin, Linda K.; Syvertsen, Erik E. (Phycologia, 1994)
A new araphid diatom genus, Synedropsis Hasle, Medlin et Syvertsen, is described from sea ice. The generitype, Synedropsis hyperborea (Grunow) Hasle, Medlin et Syvertsen from the Arctic, was first described as a species of Synedra, as was the antarctic Synedropsis fragilis (Manguin) Hasle, Syvertsen et Medlin. A second antarctic species of Synedropsis is a new combination of Cymatosira laevis Heiden in Heiden & Kolbe. In addition four new taxa, S. hyperboreoides Hasle, Syvertsen et Medlin, S. recta Hasle, Medlin et Syvertsen, S. lata Hasle, Medlin et Syvertsen and S. lata var. angustata Hasle, Medlin et Syvertsen are described from the Antarctic. The valve wall is laminar with uniseriate, often poorly developed striae and a wide sternum. Each valve possesses apical fields composed of slits. A labiate process is positioned near one apical slit field. The valve outline for most species exhibits considerable stadial variation. The girdle has several bands, most with one row of poroids close to the pars interior. Thus Synedropsis is closely related to the marine Fragilaria striatula Lyngbye except in the structure of the apical fields and the number of bands. Species observed in uncleaned material appeared in stellate or, more seldom, ribbon-shaped colonies. Synedropsis hyperborea is a common epiphyte on the ice-associated Melosira arctica Dickie in the Arctic. The antarctic species were found mainly in the bottom ice community, S. fragilis as an epiphyte on other diatoms.
Keywords: Rosshavet; Sørishavet; Weddellhavet; botanikk; diatomeer; havis; kiselalger; marin biologi; plankton

Occurrence of Pseudoterranova decipiens (Nematoda) in fish from the Southeastern Weddell Sea (Antarctic) - Palm, Harry; Andersen, Karin; Klöser, Heinz; Plötz, Joachim (Polar Biology, 1994)
Eleven fish species from the Weddell Sea (Antarctic) were examined for infestation with anisakid nematodes. Two species of the genus Contracaecum and the sealworm Pseudoterranova decipiens were isolated from the liver and the body cavity of fish affected. Only two specimens of P. decipiens (1.4%) partly invaded the belly flaps. The following fish species were infested by P. decipiens at the given prevalences: Cygnodraco mawsoni (74.4%), Trematomus scotti (23.2%), Pagetopsis maculatus (10.0%), Cryodraco antarcticus (7.1%), Trematomus lepidorhinus (3.0%), and Dolloidraco longedorsalis (2.7%). All of these, except Trematomus scotti, are new host records. Chaenodraco wilsoni, Chionodraco myersi, Gerlachea australis, Racovitzia glacialis and T. eulepidotus were not infested. The reasons for low prevalence and intensity of infestation are seen in the difficulties of P. decipiens in completing its benthic life cycle in the Weddell Sea environment, in the absence of shallow coastal waters due to the floating shelf-ice. Cygnodraco mawsoni is a crucial intermediate host, without which completion of the parasite life cycle might not be possible. In order to clarify the taxonomical position of Antarctic Pseudoterranova, morphological comparisons with specimens of P. decipiens from the German and Norwegian coast were made using scanning electron microscopy. Results revealed no differences; hence, all specimens studied belong to the same species P. decipiens.
Keywords: Sørishavet; Weddellhavet; biodiversitet; fisker; marin biologi; økologi

Norwegian Antarctic whaling seen through the eye of the camera - Barr, Susan (Whaling and history : perspectives on the evolution of the industry, 1993)
Keywords: Norge; Sørishavet; fotografi; historie; hvalfangere; hvalfangst; hvalfangststasjoner; hvalkokeri; pelagisk

A century of German interests in modern whaling, 1860s-1960s - Barthelmess, Klaus (Whaling and history : perspectives on the evolution of the industry, 1993)
Keywords: Nordmenn; Sørishavet; Tyskland; hvalfangere; pelagisk hvalfangst; økonomi

Survival against all odds? Shore station whaling at South Georgia in the Pelagic. Era, 1925-1960 - Basberg, Bjørn L (Whaling and history : perspectives on the evolution of the industry, 1993)
Keywords: Norge; Sørishavet; hvalfangere; hvalfangst; hvalfangststasjoner; hvalkokeri; pelagisk; økonomi; økonomisk historie

Den farlige isen i Antarktis - Ekra, Siv Ingrid Skau (Norges teknisk-naturvitenskapelige universitet SINTEF, 1993)
All is i antarktiske havområder er flerårig under den antarktiske sommeren. Slik is er særlig sterk og hard og smelter ikke. I store bølger får de farlige stykkene stor fart. Treffer de en båt, skjer det med stor kraft.
Keywords: Sørishavet; båter; isforholdene; populærvitenskap

Hvalfangstlæge for 40 år siden - Husby, Jakob; Kolltveit, Bård (Norsk sjøfartsmuseum. Årsberetning, 1993)
Keywords: Anglo Norse ekspedisjonene; Sørishavet; erindringer; historie; hvalfangst; hvalkokerier; pelagisk

Kapittel 3 - Arbeidsløsheten. Kapittel 6 - Den lokale organisasjonen i 30-åra - Magdahl, Jørn (Framnæsarbeidernes historie, 1993)
Keywords: Sørishavet; Vestfold; arbeiderbevegelse; byhistorie; hvalfangere; hvalfangstindustri; hvalindustri; næringsliv

Ice algae during EPOS, leg 1: assemblages, biomass, origin and nutrients - Syvertsen, Erik E; Kristiansen, Svein (Polar Biology, 1993)
Keywords: Sørishavet; Weddellhavet; alger; biomasse

Vel blåst! : kommandør Chr. Christensens hvalfangstmuseum 75 år : 1917-1992 - Wexelsen, Einar (Kommandør Chr. Christensens hvalfangstmuseum, 1993)
Keywords: Christen Christensen; Norge; Sørishavet; historie; hvalfangst; hvalindustri; museer

Working Conditions and Work-related Injuries and Illnesses on board Norwegian Floating Factories after World War II - Wexelsen, Einar (Whaling and history : perspectives on the evolution of the industry, 1993)
Keywords: Sørishavet; arbeidsforhold; hvalfangere; hvalfangst; hvalfangststasjoner; hvalkokeri; medisin

Hvalfangsten : eventyret tar slutt - Bakka, Dag (Krohn Johansen, 1992)
Keywords: Norge; Sørishavet; båter; ekspedisjoner; historie; hvalfangerselskapet; hvalfangstindustri; hvalindustri; hvalkokerier; pelagisk; skip

Phytoplankton distribution in relation to sea ice, hydrography and nutrients in the northwestern Weddell Sea in early spring 1988 during EPOS - Bianchi, Franco; Boldrin, Alfredo; Cioce, F; Dieckmann, Gerhard Stephan; Kuosa, Harri; Larsson, A M; Nöthig, Eva-Maria; Sehlstedt, P I; Socal, Giorgio; Syvertsen, Erik E (Polar Biology, 1992)
Phytoplankton biomass and distribution of major phytoplankton groups were investigated in relation to sea ice conditions, hydrography and nutrients along three north-south transects in the north western Weddell Sea in early spring 1988 during the EPOS Study (European Polarstern Study), Leg 1. Three different zones along the transects could be distinguished: 1) the Open Water Zone (OWZ) from 58-degrees to 60-degrees-S with high chlorophyll a concentrations up to 3.5-mu-g l-1; 2) the Marginal Ice Zone (MIZ) from 60-degrees to about 62.5-degrees with chlorophyll a concentrations between 0.1 and 0.3-mu-g l-1, and 3) the closed pack-ice zone (CPI) from 62.5-degrees to 63.2-degrees-S with chlorophyll a concentrations below 0.1-mu-g l-1. Nutrient concentrations increased towards the south showing winter values under the closed pack-ice. Centric diatoms such as Thalassiosira gravida and Chaetoceros neglectum forming large colonies dominated the phytoplankton assemblage in terms of biomass in open water together with large, long chain forming, pennate diatoms, whereas small pennate diatoms such as Nitzschia spp., and nanoflagellates prevailed in ice covered areas. Fairly low concentrations of phytoplankton cells were encountered at the southernmost stations and many empty diatom frustules were found in the samples. The enhanced phytoplankton biomass in the Weddell-Scotia-Confluence area is achieved through sea ice melting in the frontal zone of two different water masses, the Weddell and the Scotia Sea surface waters.
Keywords: Sørishavet; Weddellhavet; biomasse; diatomeer; fytoplankton; havis; hydrografi; marin biologi; oseanografi

Ecology of sea ice biota. 1. Habitat, terminology, and methodology - Horner, Rita; Ackley, Stephen F.; Dieckmann, Gerhard S.; Gulliksen, Bjorn; Hoshiai, Takao; Legendre, Louis; Melnikov, Igor A.; Reeburgh, William S.; Spindler, Michael; Sullivan, Cornelius W. (Polar Biology, 1992)
Polar regions are covered by extensive sea ice that is inhabited by a variety of plants and animals. The environments where the organisms live vary depending on the structure and age of the ice. Many terms have been used to describe the habitats and the organisms. We here characterize the habitats and communities and suggest some standard terms for them. We also suggest routine sampling methods and reporting units for measurements of biological and chemical variables.
Keywords: Sørishavet; biodiversitet; havis; marin biologi; polarområdene; økologi

Nitrogen uptake in the Weddell Sea during late winter and spring - Kristiansen, Svein; Syvertsen, Erik E; Farbrot, Tove (Polar Biology, 1992)
Keywords: Sørishavet; Weddellhavet; alger; biologi

Glaciomarine turbidite and current controlled deposits in Prydz Bay, Antarctica - Kuvaas, Berit; Leitchenkov, German (Marine Geology, 1992)
A thick sequence (up to 2200 m) of presumed post late Eocene/early Oligocene glaciomarine sediments is inferred to be present on the Prydz Bay continental rise. In the absence of information from drillholes, we correlate to ODP Leg 119 drillsites on the shelf and compare with the seismic reflection pattern of glaciomarine sequences in the Weddell Sea. The inferred glaciomarine sediments in Prydz Bay appear to be deposited in a complex manner, suggesting interaction by both turbidity cur rents and strong bottom currents. Reflection seismic profiles from the lower continental slope and rise shows an abundance of current influenced deposits, such as sediment waves and large sediment ridges with similarities to contourite drifts. In addition, large channel-levee complexes are abundant, suggesting deposition by turbidity currents and other massflow processes. Large channels and sediment ridges trend oblique to the continental margin. The geometry and character of the seismic reflection pattern suggest that the ridges have been deposited under the combined influence of overflow from downslope channelized turbidity currents and strong bottom water flow. The observed sediment waves and the difference along eastern and western channel margins suggest that bottom currents are flowing towards the west. We suggest that the initiation of turbidite sedimentation occurred in the late Eocene-early Oligocene, when the Amery Ice Shelf reached the shelf edge for the first time. Onset of current controlled deposition may possibly be related to the opening of the Drake Passage at the Oligocene/Miocene boundary.
Keywords: Sørishavet; Weddellhavet; havbunnen; kontinentalmargin; marin geologi

Ecology of sea ice biota. 2. Global significance - Legendre, Louis; Ackley, Stephen F.; Dieckmann, Gerhard S.; Gulliksen, Bjørn; Horner, Rita; Hoshiai, Takao; Melnikov, Igor A.; Reeburgh, William S.; Spindler, Michael; Sullivan, Cornelius W. (Polar Biology, 1992)
The sea ice does not only determine the ecology of ice biota, but it also influences the pelagic systems under the ice cover and at ice edges. In this paper, new estimates of Arctic and Antarctic production of biogenic carbon are derived, and differences as well as similarities between the two oceans are examined. In ice-covered seas, high algal concentrations (blooms) occur in association with several types of conditions. Blooms often lead to high sedimentation of intact cells and faecal pellets. In addition to ice-related blooms, there is progressive accumulation of organic matter in Arctic multi-year ice, whose fate may potentially be similar to that of blooms. A fraction of the carbon fixed by microalgae that grow in sea ice or in relation to it is exported out of the production zone. This includes particulate material sinking out of the euphotic zone, and also material passed on to the food web. Pathways through which ice algal production does reach various components of the pelagic and benthic food webs, and through them such top predators as marine mammals and birds, are discussed. Concerning global climate change and biogeochemical fluxes of carbon, not all export pathways from the euphotic zone result in the sequestration of carbon for periods of hundreds of years or more. This is because various processes, that take place in both the ice and the water column, contribute to mineralize organic carbon into CO2 before it becomes sequestered. Processes that favour the production and accumulation of biogenic carbon as well as its export to deep waters and sequestration are discussed, together with those that influence mineralization in the upper ice-covered ocean.
Keywords: Sørishavet; biodiversitet; biogeokjemi; havis; karbondioksid; klimaendringer; marin biologi; polarområdene; økologi

Hvalfangerkoner og barn forteller : hjemmeliv fra 1930-1967 - Vesterlid, Jorunn (Vestfold grafiske, 1992)
Keywords: Sørishavet; Vestfold; etnologi; hvalfangere; hvalfangst; kulturhistorie; kvinner

The role of the microbial loop in Antarctic pelagic ecosystems - Azam, Farooq; Smith, David C; Hollibaugh, James T (Polar Research, 1991)
Keywords: Sørishavet; fytoplankton; oseanografi; økosystemer

Hvalbåter over og under vann - Basberg, Bjørn L; Nævestad, Dag (Norsk sjøfartsmuseum Årsberetning, 1991)
Keywords: Sørishavet; historie; hvalfangst; skip

Whaling or Shipping? Conflicts over the Use of the Norwegian Whaling Fleet during World War II - Basberg, Bjørn Lorens (International Journal of Maritime History, 1991)
When the United Kingdom entered World War n in September 1939 the Norwegian merchant marine was immediately affected, as its ships became the targets of German submarines. Between September 1939 and April 1940 (when Norway was occupied by the Nazis), more than fifty Norwegian ships were lost, mainly in the North Sea and the north Atlantic. In November 1939 an agreement was reached between the British government and the Norwegian Shipowners Association to place almost half the Norwegian merchant fleet at Britain's disposal under the so-called "charter parties scheme." The king and the Norwegian government fled to London and established a government-inexile during the German occupation, but before their departure it was decided to establish an agency in the British capital to operate and manage Norwegian shipping. It was named the Norwegian Shipping and Trade Mission (Nortraship) and became the world's largest shipowner, controlling more than one thousand ships at the outset of the war.'
Keywords: Norge; Sørishavet; andre verdenskrig; hvalbåter; hvalfangstindustri; hvalindustri; pelagisk hvalfangst

Phytoplankton-bacteria relationship in the Antarctic marine ecosystem - Billen, Gilles; Becquevort, Sylvie (Polar Research, 1991)
Keywords: Sørishavet; Weddellhavet; bakterier; biomasse; fytoplankton; marin biologi; oseanografi; økofysiologi; økosystemer

The physiology of polar marine zooplankton - Clarke, Andrew; Peck, Lloyd S (Polar Research, 1991)
Keywords: Sørishavet; marin biologi; polarområdene; zooplankton

Primary production in polar waters: relation to nutrient availability - Harrison, W G; Cota, G F (Polar Research, 1991)
Keywords: Sørishavet; fytoplankton; oseanografi

Krill Enzymes. A New Concept for Efficient Debridement of Necrotic Ulcers - Hellgren, L.; Karlstam, B.; Mohr, Viggo; Vincent, J. (International Journal of Dermatology, 1991)
The article discusses the new concept for surgery of necrotic ulcers using the krill enzymes. The krill peptide hydrolases represent a new and important alternative to mammalian or microbial enzymes for distinctive medical applications, such as debridemen.
Keywords: Sørishavet; biokjemi; krill; marin biologi; medisin; plankton

The Crary Fan: A trough-mouth fan on the Weddell Sea continental margin, Antarctica - Kuvaas, Berit; Kristoffersen, Yngve (Marine Geology, 1991)
Multichannel seismic investigations show the presence of a large trough-mouth fan deposit on the continental margin in the southern Weddell Sea. A characteristic feature of the fan is relatively few, but large canyons and/or channels which appear to have been stable for long periods. Levees associated with the channels may reach thicknesses of more than 1 km. Drilling during ODP Leg 113 recorded the presence of glaciers in East Antarctica since early Oligocene time, and the seismic stratigraphic evidence suggests that the submarine fan is largely composed of glacigenic sediments. The channel-levee systems and complexes indicate several growth phases, apparently controlled by glacial/interglacial climate fluctuations, with maximum fan growth during glacial periods. The present interglacial period is characterized by strong and erosive flow of Ice Shelf Water running down the western slope of the fan and carrying only minor amounts of suspended matter. The fan is essentially sediment starved during interglacial periods. The dimensions of the channel-levee complexes and the persistent loci of sediment supply suggest that turbidite sedimentation resulted from melting of wet-based glaciers at or near the shelf edge, which has consequently prograded 70-80 km seaward.
Keywords: Sørishavet; Weddellhavet; havbunnen; isshelf; kontinentalmargin; kontinentalsokkel; marin geologi; seismologi

Microbial communities from the sea ice and adjacent water column at the time of ice melting in the northwestern part of the Weddell Sea - Mathot, Sylvie; Becquevort, Sylvie; Lancelot, Christiane (Polar Research, 1991)
Keywords: Sørishavet; Weddellhavet; alger; bakterier; diatomeer; havis; mikrobiologi; protozo; sjøis; smelting

Hvalfangernes mat til hverdag og fest - Ringstad, Jan Erik (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1991)
Keywords: Sørishavet; ernæring; hvalfangst

Light and productivity of phytoplankton in polar marine ecosystems: a physiological view - Sakshaug, Egil; Slagstad, Dag (Polar Research, 1991)
Keywords: Sørishavet; fysiologi; fytoplankton; planteplankton; polarområdene

Factors controlling the development of phytoplankton blooms in the Antarctic Ocean — a mathematical model - Sakshaug, Egil; Slagstad, Dag; Holm-Hansen, Osmund (Marine Chemistry, 1991)
A mathematical model describing the development of phytoplankton blooms as a function of the depth of the wind-mixed layer, spectral distribution of light, passage of atmospheric low-pressure systems, size of the initial phytoplankton stock and loss rates is presented. Model runs represent shade-adapted, large-celled, bloom-forming diatoms. Periodic deep mixing caused by strong winds may severely retard the development of blooms and frequently abort them before macronutrients are completely exhausted. Moderate depths of mixing (40-50 m) in combination with a moderately large total loss rate (about 0.01 3 h-1) can prevent blooms from developing during the brightest time of the year. Complete exhaustion of macronutrients in the upper waters is likely only if the wind-mixed layer is less than 10 m deep, i.e. in very sheltered waters, and also in the marginal ice zone when ice is melting. We do not exclude the possibility of control of phytoplankton biomass by iron in ice-free, deep-sea parts of the Antarctic Ocean, but the implied enhancement of export production through addition of iron might be restricted because of limitation by light, i.e. vertical mixing.
Keywords: Scotiahavet; Sørishavet; fytoplankton; marin biologi; oseanografi

Observations of ice shelf water at the southern Weddel sea shelf break - Foldvik, Arne; Gammelsrød, Tor; Nordlund, Nina; Nytun, Kjell (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: NARE 1989/90; Sørishavet; Weddellhavet; ekspedisjoner; forskning; isshelf; oseanografi

The tides of the southern Weddell Sea - Foldvik, Arne; Middleton, Jason H; Foster, Theodore D (Deep Sea Research Part A. Oceanographic Research Papers, 1990)
Keywords: Sørishavet; Weddellhavet; isshelf; kontinentalsokkel; kontinentalsokler; tidevann

Marine biological studies in the Weddel sea and north of Dronning Maud Land - Gulliksen, Bjørn; Lønne, Ole Jørgen; Hellum, Cecilie (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: NARE 1989/90; Sørishavet; Weddellhavet; marin biologi

Microbial autotrophic and heterotrophic eucaryotes in Antarctic waters: relationships between biomass and chlorophyll, adenosine triphosphate and particulate organic carbon - Hewes, Christopher D.; Sakshaug, Egil; Reid, Freda M. H.; Holm-Hansen, Osmund (Marine Ecology Progress Series, 1990)
Microscopical examination of near-surface eucaryotic microbial populations in circumcontinental waters of Antarctica indicated that nanoplankton (<20 μm diameter) dominated in regions with low chlorophyll concentrations (< 1 μg l⁻¹). About 30 % of the mean nanoplankton carbon consisted of heterotrophic flagellates. Heterotrophic microplankton carbon (> 20 μm diameter) was generally less significant. The variation in phytoplankton biomass was the result primarily of changes in cell density of pennate diatoms in the East Wind Drift, and of centric diatoms in the Weddell Sea and the Scotia Ridge region. Autotrophic and heterotrophic carbon as determined by microscopical analysis were compared with data for total particulate carbon, chlorophyll a, and adenosine triphosphate. Estimates for the C:chl ratio of autotrophs increased with decreasing concentrations of chlorophyll a, with mean values of 46 in bloom waters and 144 in 'blue water'. A C:ATP ratio for heterotrophic nanoplankton was estimated to be about 100, while that for heterotrophic microplankton may be lower. Algorithms, incorporating concentrations of chlorophyll a and ATP, are described which allow estimates of autotrophic and heterotrophic microbial biomass.
Keywords: Sørishavet; alger; biomasse; fytoplankton; marin biologi; oseanografi; plankton; zooplankton

I hjertet av Antarktis; Norge i Antarktis - Imbert, Bertrand C; Hem, Arne (Polarforskningens pionerer, 1990)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Norge; Peter I. Øy; Roald Amundsen; Sydpolsekspedisjonen; Sørishavet; hvalfangst; oppdagelsesreiser

La oss arbeide! : A/S Laboremus gjennom 80 år 1910-1990 - Kolltveit, Bård ([A/S Laboremus], 1990)
Keywords: Norge; Sørishavet; hvalfangstindustri; hvalindustri; rederier; sjøfartshistorie

Ingeniør Sæbjørnsens bukspretter - Ringstad, Jan Erik (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1990)
Keywords: Nordmenn; Sørishavet; hvalfangst; hvalfangstindustri; hvalindustri; patenter; pelagisk; utstyr

Næringer i hvalfangstens grenseland - Ringstad, Jan Erik (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1990)
Keywords: Christen Christensen; Sørishavet; historie; hvalfangst; hvalkokerier; hvalolje; næring; patenter; pelagisk; økonomi

Oxygen 18 and helium as tracers of ice shelf water and water/ice interaction in the Weddell Sea - Schlosser, Peter; Bayer, Reinhold; Foldvik, Arne; Gammelsrød, Tor; Rohardt, Gerd; Münnich, Karl Otto (Journal of Geophysical Research: Oceans, 1990)
Oxygen 18 and helium isotope data from stations located in the Filchner Depression, on the continental slope of the southern Weddell Sea, and in the central Weddell Sea are presented and discussed. The 18O and 4He signals imprinted on the water circulating under the Filchner/Ronne Ice Shelf (Ice Shelf Water, or ISW) due to melting of glacial ice at the base of the ice shelf are traced across the sill separating the Filchner Depression from the Weddell Sea. Low δ18O values are correlated with high 4He concentrations in the ISW found in the Filchner Depression (minimum δ18O values: −0.8‰; maximum 4He concentrations: about 4.7×10−8 cm3 STP g−1). The fraction of glacial meltwater contained in the ISW found in the Filchner Depression is estimated to about 6 to 7‰. The 18O and helium isotope data from the overflowing shelf water component observed on the continental slope confirm the hypothesis that ISW contributes significantly to the Weddell Sea Bottom Water (WSBW). On the basis of a inultiparameter water mass analysis it is discussed which fraction of the WSBW originates from ISW and which other shelf waters potentially could contribute to WSBW.
Keywords: Sørishavet; Weddellhavet; brehylle; geofysikk; hydrografi; isbrem; isshelf; oseanografi; smeltevann; vannmasser

Zwischen Kooperation und Konfrontation. Deutschland, Norwegen und die Walfangfrage in den 1930er Jahren - Scholl, Lars Ulrich (Sjøfartshistorisk årbok : Norwegian yearbook of maritime history, 1990)
Keywords: Norge; Sørishavet; Tyskland; historie; hvalfangere; hvalfangstindustri; hvalolje; pelagisk; samarbeid

Marine geological studies in the Weddel sea - Sjøholm, Jorunn; Jansen, Eystein (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: NARE 1989/90; Sørishavet; Weddellhavet; ekspedisjoner; forskning; marin geologi

På hvalfangst med blyant og farvestifter - Wexelsen, Einar (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1990)
Keywords: Nordmenn; Sørishavet; historie; hvalfangst; kunst; pelagisk

Pierce's kastebørse - et "Reodor Felgen" -patent med lang levetid - Wexelsen, Einar (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1990)
Keywords: Sørishavet; historie; hvalfangst; hvalolje; patenter; pelagisk; utstyr

Cold resistance and metabolic responses to salinity variations in the amphipod Eusirus antarcticus and the krill Euphausia superba - Aarset, Arne V.; Torres, Joseph J. (Polar Biology, 1989)
The krill Euphausia superba, unlike the amphipod, Eusirus antarcticus, tolerates being frozen into solid sea-ice at temperatures down to about-4°C. Cooled in air, the amphipod and the krill freeze and will die at temperatures of-11° and-9°C respectively, representing the supercooling points of the animals. The krill is an osmoconformer in the salinity range of 25 to 45 ppt, while the amphipod conforms in the salinity range of 26 to 40 ppt. The animals thereby lower the melting point of their body fluids in the vicinity of the freezing sea ice, preventing internal ice formation at low temperatures. The mean oxygen consumption rates, at raised and lowered salinities, were not significantly different from rates obtained in normal (35 ppt.) seawater, indicating that salinity has little effect on the metabolism of either species.
Keywords: Sørishavet; krepsdyr; krill; kuldetoleranse; marin biologi; plankton

Genetic homogeneity of krill (Euphausia superba Dana) in the Southern Ocean - Fevolden, Svein Erik; Schneppenheim, Reinhard (Polar Biology, 1989)
Development of a comprehensive picture of the genetic population structure of the Antarctic krill (Euphausia superba) has been hampered by a lack of genetic data from two major areas of the species' distribution, the Bellingshausen Sea and the Ross Sea. Evidence from earlier studies of a discrete “Bellingshausen Sea” population was based on anomalous allele frequencies in two sample sets that were collected near the west coast of the Antarctic Peninsula rather than in the Bellingshausen Sea proper. In this paper we describe the first biochemical genetic data obtained on krill from the central Bellingshausen Sea and from the Ross Sea. Analyses of eight polymorphic loci in samples from these two areas have failed to provide any evidence of population structuring within the Pacific sector of the Southern Ocean, and have indicated that Pacific sector krill cannot be genetically discriminated from Atlantic sector krill or Indian Ocean sector krill. These findings further support the hypothesis of a single circumpolar breeding population of Antarctic krill.
Keywords: Rosshavet; Sørishavet; biokjemi; genetikk; krill; marin biologi; plankton

Phytoplankton blooms in the vicinity of palmer station, Antarctica - Holm-Hansen, Osmund; Mitchell, Brian Gregory; Hewes, Christopher D; Karl, David Michael (Polar Biology, 1989)
Fifteen oceanographic stations were occupied in the vicinity of Anvers Island, Antarctica, in January of 1985 and 1987. All stations showed high phytoplankton biomass (4.0 to 30 μg chl-a/liter) which was either uniformly distributed in the upper mixed layer or showed a pronounced sub-surface maximum at 4–5 m depth. As phosphate was less than 0.02 μm and nitrate about 2.0 μm in surface waters, it appears that nutrient limitation of phytoplankton growth may be of importance during such blooms. This view is supported by chemical measurements of the particulate material which showed high chl-a/ATP ratios (about 7.7), as well as high POC/ATP ratios (about 700). Microscopical analysis revealed a dominance of large-celled diatoms and the near absence of heterotrophic protozoans. Size fractionation studies showed that the nanoplankton accounted for only 28% of the total phytoplankton biomass. When phytoplankton biomass reaches the levels found at these stations, it appears that the cells are light-limited and hence dark-adapted, which results in the high chl-a/ATP ratios and the low assimilation values (0.49–1.64) obtained in our studies. Under such conditions greater than 50% of the total phytoplankton biomass is found below the 1% light level.
Keywords: Sørishavet; biomasse; fytoplankton; oseanografi

En hvalfangstsesong med mange forlis. Den første "Kosmos" - Møller, Vilhelm (Kjære gamle Sandefjord, 1989)
Keywords: Sørishavet; Vestfold; erindringer; historie; hvalfangere; hvalfangstindustri; hvalindustri

Storrederiet Nortraship : handelsflåten i krig - Mossige, Erling (Grøndahl, 1989)
Keywords: Norge; Sørishavet; historie; hvalfangstindustri; hvalindustri; pelagisk; rederier; skipsfart

Hjelpekrysser kaprer norske hvalfangere - Nilsen, Tore L.; Thowsen, Atle (Sjøfartshistorisk årbok : Norwegian yearbook of maritime history, 1989)
Keywords: Sørishavet; andre verdenskrig; historie; hvalbåter; hvalfangstflåten; pelagisk

Life at the Ice Edge - Sakshaug, Egil; Skjoldal, Hein Rune (Ambio, 1989)
Keywords: Sørishavet; alger; forurensning; fytoplankton; krill; miljø; planteplankton; zooplankton

Icebergs rework shelf sediments to 500 m off Antarctica - Barnes, Peter W.; Lien, Reidar (Geology, 1988)
Icebergs and sea ice rework the sediments of high-latitude shelves, producing modern diamicts (ice-keel turbates) unrelated to glacial proximity. Off Antarctica, sidescan sonar data indicate the presence of ice-gouge features formed by the physical interaction between ice keels and the sea bed. These are recognized as incisions a few metres deep and tens of metres wide, in water depths up to 500 m. On the submarine bank tops and slopes off Wilkes Land and in the Weddell Sea, subcircular depressions 30 to 150 m in diameter, a washboard pattern, and hummocky bed features also represent iceberg-resting sites. The freshness of sea-bed morphology, nearby Holocene sediment ponding, and active hydraulic sedimentary processes indicate that the sea floor is being reworked by iceberg keels. Tabular iceberg drafts in excess of 330 m have been measured, and modeling studies suggest that nontabular iceberg drafts of 500 m are possible. We conclude that a modern ice-keel turbate deposit in the form of a poorly stratified diamicton is probably widespread on that part (54%) of the Antarctic shelf less than 500 m deep.
Keywords: Sørishavet; Weddellhavet; geofysikk; geologi; isberg; issfjell; oseanografi

Biochemical genetics and population structure of Euphausia superba - Fevolden, Svein Erik (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1988)
Keywords: Sørishavet; biokjemi; krill; plankton

Genetic population structure of Euphausia superba DANA in the Atlantic Sector of the Southern Ocean as demonstrated by different electrophoretic techniques - Fevolden, Svein Erik; Schneppenheim, Reinhard (Polar Biology, 1988)
Electrophoretic analyses of allele distributions at nine polymorphic gene loci were conducted in samples of Euphausia superba from the Bransfield Strait, off the South Orkney Islands, and from the south-eastern part of the Weddell Sea. The aim was to determine whether reported phenotypic differences between krill stocks from these areas could be linked to genotypic differences. Despite minor deviations of genotype distributions from Hardy-Weinberg expectations, the data gave no evidence of genetic heterogeneity over the sampled area, and the hypothesis of a single genetically homogeneous krill population could not be rejected. Genetic data for four selected loci were verified by using two different electrophoretic methods. Results from these two techniques yielded no discrepancies in interpretation of the data.
Keywords: Sør-Orknøyene; Sørishavet; Weddellhavet; genetikk; krill; marin biologi; plankton

Notes on Southern Ocean hydrography, sea-ice and bottom water formation - Foldvik, Arne; Gammelsrød, Tor (Palaeogeography, Palaeoclimatology, Palaeoecology, 1988)
The Southern Ocean circulation and sea-ice distribution is briefly described. The formation of extremely cold bottom water in the Weddell Sea and its relation to the floating Ronne-Filchner Ice Shelves is discussed. It is shown that a concentrated swift eroding bottom current with anomalous low ratio transports the cold and dense ice Shelf Water from the shelf towards large depths. Comments are made on possible implications of this process for the large-scale deep-water circulation and for the interpretation of sediment cores.
Keywords: Sørishavet; Weddellhavet; geofysikk; havis; havstrømmer; hydrografi; isshelf; oseanografi

Skjellressurser i Sydishavet: litteraturstudie - Jakobsen, Øystein; Fiskeridirektoratet (Norges fiskerihøyskole, 1988)
Keywords: Sørishavet; marinbiologi; skjell

Antarctic icebergs: production, distribution and disintegration (abstract) - Orheim, Olav (Annals of Glaciology, 1988)
A programme of systematic iceberg observations was initiated in 1981 by Norsk Polarinstitutt through the SCAR Working Group on Glaciology. Icebergs are recorded every 6 h and in five length groups: 10-50, 50-200, 200-500 and 500-1000 m, and those over 1000 m, which are described individually. Data on more than 100 000 icebergs are now on file at Norsk Polarinstitutt, and practically all ships travelling to and from Antarctica participate in the collection of data. This paper presents the first comprehensive analysis of the iceberg data. The quality of the data set is discussed, with consideration of potential errors in and limitations of the data, and various statistical evaluations. Representative distribution data are presented, and used to determine iceberg production, disintegration and mean residence times, and regional and total Antarctic calving rates. The incidence of large-scale calving in particular is evaluated, including the remarkably large break-offs in recent years. These exceed both the total annual accumulation on the Antarctic continent and the mean annual calving rate as determined from ship observations. The results show further: (1) that there are more than 200 000 icebergs south of the Antarctic Convergence, (2) that there are large regional differences in iceberg calving rates and iceberg sizes, and (3) that the calving rate from Antarctica is higher than that given in most previous estimates, which implies (4) that the mass balance of the Antarctic ice sheet is not positive as suggested by most recent estimates.
Keywords: Sørishavet; glasiologi

Palaeoceanography of the subantarctic South Atlantic - Ciesielski, Paul; Kristoffersen, Yngve (Nature, 1987)
Keywords: Sørishavet; oseanografi

Biochemistry of the autolytic processes in Antarctic krill post mortem. Autoproteolysis - Ellingsen, Trond E.; Mohr, Viggo (Biochemical Journal, 1987)
1. Autoproteolysis post mortem was examined at 0 degree C by following the changes in the major classes of krill (Euphausia superba and Euphausia crystallorophias) proteins and by liberation of peptides and free amino acids, and was based on experiments conducted on board expedition vessels in the Antarctic. 2. Primarily salt-soluble proteins were broken down during the first week of incubation, whereas water-soluble and insoluble proteins were degraded to a much smaller extent. The enzymes responsible for the hydrolysis presumably originate primarily from the digestive apparatus of the krill. 3. In general, the individual amino acids were released at rates corresponding to their relative occurrence in the bulk protein of the krill. Alanine was liberated in larger amounts than would be expected from the composition of the krill protein, and was evidently formed also by reactions other than proteolysis. Glutamic acid, and certain amino acids which presumably occur with high frequency adjacent to glumatic acid residues in the krill protein, were liberated only to a limited extent, and accumulated in smaller peptides. 4. During proteolysis, arginine seemed to be converted to some degree into ornithine, and on prolonged incubation conversion of arginine and lysine into their corresponding decarboxylation products, agmatine and cadaverine, appeared to take place.
Keywords: Sørishavet; biokjemi; krill; marin biologi; plankton

Geology, geophysics, and hydrocarbon potential of Antarctica continental margin of Weddell Sea - Hinz, K.; Kristoffersen, Yngve (AAPG Bulletin, 1987)
A prominent escarpment, called the Explora-Andenes Escarpment, has been recognized between long. 40°W, lat. 72°40^primeS and long. 10°W, lat. 69°20^primeS. It separates the continental margin from the Weddell Sea basin. Our recent MCS data have revealed the presence of some remarkably symmetric structures beneath a thick pile of tectonically undisturbed sediments. For example, two extensive wedge-shaped basement units occur between 20°W and 40°W. These units are characterized by a pattern of divergent reflectors which surround an elongated depression in basement. The northern wedge terminates against the Explora-Andenes Escarpment between 25°W and 30°W. The southern wedge, known as the Explora Wedge, shows a northward-dipping reflection pattern. The seismic characteristics suggest that both wedges consist of volcanic rocks. The basement depression is interpreted as a failed rift basin. The initial fragmentation of Gondwana was accompanied by prolific volcanism, which led to the emplacement of the wedges of "dipping reflectors." The tectonomagmatic/volcanic period was followed by transtensional movements between Africa and Antarctica. This phase was heralded by the formation of the Explora-Andenes Escarpment as a new plate boundary and the opening of the Weddell Sea by sea-floor spreading. The Explora-Andenes Escarpment cuts across the early rift structures. The initial fragmentation of Gondwana was accompanied by prolific volcanism, which led to the emplacement of the wedges of dipping reflectors. The tectonomagmatic/volcanic period was followed by transtensional movements between Africa and Antarctica. This phase was heralded by the formation of the Explora-Andenes Escarpment as a new plate boundary and the opening of the Weddell Sea by sea-floor spreading. The Explora-Andenes Escarpment cuts across the early rift structures.
Keywords: Antarktis; Sørishavet; Weddellhavet; geofysikk; geologi

Evolution of under water sides of ice shelves and icebergs - Orheim, Olav (Annals of Glaciology, 1987)
A systematic programme of side-scan sonar and plumb- line soundings was carried out in the Weddell Sea area in 1985 to measure the under-water sides of ice shelves and icebergs. From these observations the following model is suggested for the evolution of the ice front: (1) Initial stage: fracturing of the ice shelves takes place along smooth, curvi-linear segments with vertical faces. (2) Formative stage: the freshly formed vertical face is eroded both by wave and swell action around the water line, by small calvings from the undercut, overhanging subaerial face, and by submarine melting. The melting has a minimum at 50–100 m depth, and increases with depth to a rate of around 10 m a−1 at 200 m, This is about twice the rate of erosion at the water line. The variation in melting with depth results from a combination of summer melting by near-surface water, and year-round melting by water masses that are increasingly warmer than the pressure melting-point with depth. (3) Mature stage: this stage is reached after a few years of exposure. The backward erosion of the face leads to a shape with a prominent under-water “nose” with a maximum projection to more than 50 m at 50–100 m depth. The ramp above this slopes upwards to meet the vertical wall about 5 m below the water line. The ice below the nose is melted back beyond the above-water face. There is no net buoyancy and ice shelves at this mature stage are generally not up-warped at the front.
Keywords: Sørishavet; glasiologi

Icebergs in the Southern Ocean (abstract) - Orheim, Olav (Annals of Glaciology, 1987)
Relatively little data on the distribution of Antarctic icebergs were available prior to 1980. The published literature included size data of about 5000 icebergs, and position data of 12 000 icebergs. There were indications that the size data were biased in favour of larger icebergs. A programme of systematic iceberg observations was therefore initiated by Norsk Polarinstitutt in 198! through the SCAR Working Group on Glaciology. This programme is based on standard “blue” forms distributed to all ships going to Antarctica. The icebergs are recorded every 6 h and in Five length groups: 10–50, 50–200, 200–500, and 500–1000 m, and those over 1000 m are described individually. The amount of data has increased greatly from the start in 1981–82. The position of 70 000 icebergs, including 50 000 that had been size classified, were on file at Norsk Polarinstitutt by December 1985, and the data set is growing rapidly. Most ships travelling to and from Antarctica now participate in collection of the data. ( shows the locations of the icebergs sighted.) Fig. 1. Location of iceberg observations under the programme initiated in 1981. Main ship tracks are clearly reflected. The average observation represents 14 icebergs. The size distribution of the classified icebergs observed under this programme up to December 1985 is given in : Table I The “standard size” (length, width, and thickness) is based on our observations from three Antarctic expeditions which carried out dedicated iceberg studies. Many icebergs are of course not right-angled parallelepipedal in shape, but this is a good approximation for most of the larger icebergs. The data are based both on visual sightings and on radar observations. Duplicate observations from a ship moving at slow or zero speed are as far as possible eliminated, both during observation, and by critical appraisal before the data are filed. The data editing also includes evaluation of data quality, especially in connection with radar observations, and comparison of positions and dimensions of the large icebergs in order to reduce to a minimum repeated observations from different vessels of icebergs >1000 m. These account for most of the iceberg mass (see ). Consideration of iceberg-distribution patterns and the observed area of the Southern Ocean, and of duplicate observations, indicates more than 300 000 icebergs south of the Antarctic Convergence, with a total ice mass of about 1016 kg. Consideration of mean residence times indicates an annual iceberg production from the continent of 23–1015 kg, which is considerably higher than most other recent estimates. This also suggests that the Antarctic ice sheet is in balance. The data indicate large regional differences in iceberg sizes, the most noticeable being between the two sides of the Antarctic Peninsula, and between the Amery Ice Shelf/ Prydz Bay area and the remainder of East Antarctica. These differences are probably mainly related to different calving sites. About one-third of the observed icebergs are over the continental shelf of Antarctica. The total under-water area of these icebergs is two orders of magnitude less than the under-water area of the Antarctic ice shelves. The annual total iceberg melting and its effect on the water masses over the continental shelf has been calculated from ocean-water temperature variations at 200 m depth and estimated melt rates. This turns out to be an order of magnitude less than the annual effect of melting sea ice. The iceberg data considered here are probably under-represented with respect to the smallest sizes, and they do not include icebergs that have become <10 m. Inclusion of these ice bodies would increase the total melt.
Keywords: Sørishavet; glasiologi

Motortankskipenes inntog. En komparasjon av utviklingen i dansk, norsk og svensk skipsbyggingsindustri, ca. 1912 til 1933 - Basberg, Bjørn L (Sjøfartshistorisk årbok : Norwegian yearbook of maritime history, 1986)
Keywords: Sørishavet; historie; hvalbåter; hvalfangstindustri; pelagisk; skipsbyggerier; skipsfart

Da hvalfangerne organiserte seg. Forholdet mellom sosial mobilitet og organisering - Devig, Thor N (Sandefjordmuseene. Årbok, 1986)
Keywords: Sørishavet; arbeidsforhold; fagforbund; fagforeninger; hvalfangere; hvalfangst; hvalfangststasjoner; hvalkokeri

Genetic variation of Euphausia superba Dana in the Antarctic Peninsula waters - Fevolden, Svein Erik (Sarsia, 1986)
Nine samples of Antarctic krill collected at seven localities in the Palmer Archipelago and Bransfield Strait west of the Antarctic Peninsula were analysed for genetic variation at eight enzyme loci. Despite significant among sample heterogeneity in allele frequencies, no convincing evidence was found to support the hypothesis of distinct genetic stocks of Euphausia superba in the investigated area. Allele frequency distributions could not be correlated to regional differences in size patterns. Allelic proportions at the PGI locus did not indicate that the investigated krill was genetically different from E. superba from the Weddell Sea region (from earlier investigations). Deviations of genotypes, or allele frequencies from those expected under Hardy-Weinberg equilibrium, however, may indicate regional, or yearly variation due to occasional selection.
Keywords: Sørishavet; Weddellhavet; genetikk; krill; plankton

Proteases of Antarctic krill—a new system for effective enzymatic debridement of necrotic ulcerations - Hellgren, L.; Mohr, Viggo; Vincent, J. (Experientia, 1986)
The Antarctic krill (Euphausia superba) possesses an ‘over-dimensioned’ digestive system, which is of vital importance for the survival of this euphaucean shrimp in the extreme marine environment. The isolated enzymes contain a well-balanced mixture of both endo- and exopeptidases, assuring fast and complete breakdown of proteinaceous material. These unique properties have now been shown to be extremely valuable for the effective removal of necrotic debris, fibrin or blood crusts in vitro. Therefore the krill enzymes should be considered as an important resource in the future management of necrotic wounds.
Keywords: Sørishavet; biokjemi; krill; marin biologi; medisin; plankton

Norge i Antarktis - Luraas, Ragnar; Kjærvik, Atle (Norsk journalisthøgskole, 1986)
Keywords: Antarktis; Sørishavet; historie; hvalfangst; politikk

Hydrolysis of proteins by peptide hydrolases of Antarctic krill, Euphausia superba - Osnes, Knut Kristian; Ellingsen, Trond E.; Mohr, Viggo (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1986)
1. The hydrolysis of casein by peptide hydrolases of Antarctic krill, E. superba, has been 2. The peptide hydrolases studied included trypsin-like enzymes, carboxypeptidase A-type of enzymes, carboxypeptidase B-type of enzymes, and an aminopeptidase isolated from Antarctic krill. 3. The trypsin-like enzymes seemed to play a decisive role in the degradation of casein, whereas the carboxypeptidase A, carboxypeptidase B and the aminopeptidase had limited effect when acting on casein alone. When combined with the trypsin-like enzymes, the exopeptidases effected enhanced release of amino acids from the protein. 4. Based on the pattern of amino acids relased from casein by a crude extract of krill, and by the isolated peptide hydrolases either alone or in combination, it is concluded that the purified peptide hydrolases examined comprise the major enzymes responsible for the autoproteolytic activity of krill at neutral- to weakly alkaline pH.
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; Sørishavet; biokjemi; krill; marin biologi; plankton

On the purification and characterization of exopeptidases from Antarctic krill, Euphausia superba - Osnes, Knut Kristian; Mohr, Viggo (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1986)
1. Two carboxypeptidase-A type of enzymes and two carboxypeptidase-B type of enzymes effecting hydrolysis of Hipp-l-Phe and Hipp-l-Arg respectively, have been purified from E. superba using gel filtration, affinity chromatography and FPLC-anion exchange chromatography. In addition an aminopeptidase has been partly purified. 2. The carboxypeptidases had mol. wts of 27,000 (carboxypeptidase A) and 31,000 (carboxypeptidase B). 3. Carboxypeptidase A exhibited a broad pH optimum with a maximum at pH 5.5–6.5, whereas carboxypeptidase B had a more narrow pH-optimum with a maximum at pH 7. The aminopeptidase had an optimum at about pH 8.7. 4. The carboxypeptidases were inhibited by the chelating agent 1,10-phenanthroline.
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; Sørishavet; biokjemi; krill; marin biologi; plankton

Photoadaptation in Antarctic phytopfankton: variations in growth rate, chemical composition and P versus I curves - Sakshaug, Egil; Holm-Hansen, Osmund (Journal of Plankton Research, 1986)
The response of phytoplankton to variations in the light regime was studied during the VULCAN and ACDA cruises in the Antarctic. Unenriched batch cultures of 12–19 days' duration reached chl concentrations of 10–50 μg−1 and exhibited exponential growth rates, with the maximal rate being 0.41 doubl, day−1. Ice edge algae exhibited maximum growth rates at photon flux densities (PFD) of 30–100 μE m−2S−1 and the growth rate was reduced by about 30% at 500–1000 μE m−2S−1 The chl/C ratio ranged between 0.004 and 0.018, with the lowest ratios at PFDs above 500 μE m−2S−1 chl/C ratios were also below maximum at PFDs below 40–50 μE m−2S−1 The C:N:P ratios were close to the Redfield ratios; the Si/C ratio averaged 0.16 (atoms), and the ATP/C ratio averaged from 0.0024 to 0.0050 in different culture senes. When thawed after having been frozen for 10 days, shade-adapted cultures were in a much better condition than sun-adapted ones. P versus I data showed that the maximum assimilation number varied from 0.75 to 4.4 μg C (μg chl)−1h−1. It varied inversely with the chl/C ratio; therefore the maximum carbon turnover rate varied little between samples (0.024/0.035 h−1). Low biomass communities exhibited relatively high values for α (the initial slope of P versus I curves), low values for 1sat (160–330 μE m−2S−1), and they were susceptible to photoinhibition. In contrast, communities dominated by Odontella weissflogii exhibited low values for α, a high value for Isat (560 μE m−2S−1 and they tolerated high PFDs. The photo-adaptational status of the phytoplankton in natural water samples is discussed relative to the profile of water column stability and mixing processes.
Keywords: Sørishavet; alger; biokjemi; fytoplankton; marin biologi; oseanografi; planteplankton

Suksess i syd: utvidet forskning i Antarktis (Forsvarets forum, 1985)
Keywords: Antarktis; Bouvetøya; Sørishavet; ekspedisjoner; forskning; logistikk

Aleksandr Stepanovich Kuchin: the Russian who went south with Amundsen - Barr, William (Polar Record, 1985)
Aleksandr Stepanovich Kuchin (1888–1912) was already an experienced mariner and oceanographer when Amundsen invited him to join the Fram expedition of 1910–12. Expecting a voyage through the Barents Sea, Kuchin found himself on an expedition to the Antarctic. While Amundsen's sledging parties sought the South Pole, Kuchin remained with the ship, completing an excellent oceanographic survey of the southern Atlantic Ocean. Returning to Russia in 1912 he was recruited, by the geologist and explorer V. A. Rusinov to join a scientific expedition to Svalbard. As deputy leader of the party and captain of Gerkules, the expedition ship, Kuchin played an important role in the Svalbard survey. Then once again found himself heading in an unexpected direction: on completing the Svalbard work, Rusanov decided to attempt the Northern Sea Route to the Bering Strait. Gerkules disappeared and was never seen again; her loss, presumably in the Kara Sea, brought to an untimely end the career of a promising young polar explorer.
Keywords: Roald Amundsen; Sydpolsekspedisjonen; Sørishavet; biografier; oseanografi; polarområdene

Technological transformation in the Norwegian whaling industry in the interwar period - Basberg, Bjørn L (Scandinavian Economic History Review, 1985)
Inventions, innovations and technological changes in the broadest sense are often treated as an independent process and are not subjected to any detailed attempts at explanation. It is scarcely anything exceptional, for example, that Sigurd Risting, the first historian of the whaling industry in Norway, explains the development of whaling as follows: Thus there has been a large stock of finback whales along the coast of Norway for hundreds of years without their having been an object of regular profitable hunting. The reason for this has been nothing more than lack of tackle and methods capable of making hunting possible. The moment these become available, whaling as a rational business will arise by itself out of natural necessity, so to speak." Bjern L. Basberg, b. 1952, is a research fellow in economic history at the Norwegian School of Economic and Business Administration. The article is based on a thesis of 1980 titled: Innovasjons-teori, patenter og teknologisk utvikling i norsk hvalfangst ca. 1860-1968.
Keywords: Norge; Sørishavet; hvalfangst; pelagisk; teknologi; økonomi

Hydrographic observations on the southern Weddell Sea shelf break - Foldvik, Arne; Gammelsrød, Tor (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: NARE 1984/85; Sørishavet; Weddellhavet; hydrografi; oseanografi

Oceanographic conditions on the Weddell Sea Shelf during the German Antarctic Expedition 1979/80 - Foldvik, Arne; Gammelsrød, Tor; Slotsvik, Noralf; Tørresen, Tor (Polar Research, 1985)
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; hydrografi; isshelf; oseanografi

Circulation and Water Masses on the Southern Weddell Sea Shelf - Foldvik, Arne; Gammelsrød, Tor; Tørresen, Tor (Oceanology of the Antarctic Continental Shelf, 1985)
Keywords: Sørishavet; Weddellhavet; forskning; havstrømmer; oseanografi

Hydrographic observations from the Weddell Sea during the Norwegian Antarctic Research Expedition 1976/77 - Foldvik, Arne; Gammelsrød, Tor; Tørresen, Tor (Polar Research, 1985)
Keywords: Sørishavet; Weddellhavet; hydrografi; kontinentalsokkel; observasjoner

Physical oceanography studies in the Weddell Sea during the Norwegian Antarctic Research Expedition 1978/79 - Foldvik, Arne; Gammelsrød, Tor; Tørresen, Tor (Polar Research, 1985)
Keywords: Sørishavet; Weddellhavet; havstrømmer; hydrografi; isshelf; oseanografi

Bottom Currents Near the Continental Shelf Break in the Weddell Sea - Foldvik, Arne; Kvinge, Thor; Tørresen, Tor (Oceanology of the Antarctic Continental Shelf, 1985)
Keywords: Sørishavet; Weddellhavet; bunnvann; havstrømmer; kontinentalsokkel; kontinentalsokler; tidevannsstrømmer

Geophysical studies in the southern Weddell Sea - Haugland, Kristen; Kristoffersen, Yngve (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: NARE 1984/85; Sørishavet; Weddellhavet; geofysikk

Iceberg research and other glaciological studies from K/V "Andenes" - Kristensen, Monica; Orheim, Olav (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: NARE 1984/85; Sørishavet; Weddellhavet; glasiologi; isfjell

Impact of Grounded Icebergs on the Hydrographic Conditions Near the Filchner Ice Shelf - Nøst, Ole Anders; Østerhus, Svein (Ocean, Ice, and Atmosphere: Interactions at the Antarctic Continental Margin, 1985)
Keywords: Sørishavet; Weddellhavet; havis; hydrografi; isberg; isfjell; isshelf; sjøis; vannmasser

On the purification and characterization of three anionic, serine-type peptide hydrolases from antarctic krill, Euphausia Superba - Osnes, Knut Kristian; Mohr, Viggo (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1985)
1. Three enzymes effecting hydrolysis of TAME have been purified from E. superba using gel filtration, affinity chromatography and FPLC-anion exchange chromatography. 2. The enzymes had molecular weights of 30,000 (Enzyme I), and 31,000 (Enzymes II and III), respectively, as estimated from SDS-PAGE. 3. pH-optima of about 8.2 were observed for all three enzymes. 4. The enzymes were inhibited by phenyl methyl sulphonyl fluoride (PMSF), tosyl lysyl chloromethyl ketone (TLCK) and soybean trypsin inhibitor (SBTI), whereas tosyl phenyl chloromethyl ketone (TPCK) had no effect on the activity. 5. The enzymes were stable at neutral pH, and only slowly inactivated at highly alkaline pH. Low pH rapidly inactivated all three enzymes. 6. Enzyme I liberated amino acids from casein, whereas Enzymes II and III did not; the latter two being true endopeptidases which effected enhanced amino acid production from casein when mixed with Enzyme I.
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; Sørishavet; biokjemi; krill; marin biologi; plankton

Peptide hydrolases of Antartic krill, Euphausia superba - Osnes, Knut Kristian; Mohr, Viggo (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1985)
1. A survey has been made of the peptide hydrolase activities occurring in Antarctic krill, Euphausia superba. 2. A major protein hydrolyzing activity in the pH range of 6–8, and a minor activity at pH 3–4, were detected. 3. Temperature optima of approx. 50°C and 35–40°C, respectively were determined for the neutral and acid peptide hydrolases. 4. Trypsin-like activity, as well as carboxypeptidase A-, carboxypeptidase B-, and aminopeptidase activity were detected in extracts of krill. 5. Considerable variation in total hydrolase activity was observed in different catches of E. superba obtained from the same area. 6. The pattern of release of amino acids during autolytic breakdown of krill proteins was very similar in catches of krill exhibiting considerable differences with respect to total peptide hydrolase activity.
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; Sørishavet; biokjemi; krill; marin biologi; plankton

The distribution of lipid in the tissues of Antarctic krill, Euphausia superba - Saether, Olav; Ellingsen, Trond E.; Mohr, Viggo (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1985)
1. The distribution of lipid in the tissues of Euphausia superba has been examined by histological and chemical methods. 2. The total lipid content of krill from different catches may vary considerably, and the variations are probably due both to differences in nutritional status and maturity of the roe of female krill. 3. Female krill contained about twice as much lipid as male krill from the same haul. 4. The roe is the dominating lipid depot in female krill; in both male and female krill lipid-rich areas are found along the digestive tract, between muscle bundles and beneath the exoskeleton. 5. Both the phosphoglyceride- and triacylglycerol content of body fractions of E. superba varied in proportion to the total lipid content, thus supporting the contention that both phosphoglycerides and triacylglycerols serve as depot lipids in this species of krill.
Keywords: Sørishavet; biokjemi; krill; marin biologi; plankton

Marine geological studies on the Weddel Sea shelf - Solheim, Anders; Kristoffersen, Yngve (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: NARE 1984/85; Sørishavet; Weddellhavet; marin geologi

Resting spore formation in the antarctic diatoms Coscinodiscus furcatus Karsten and Thalassiosira australis Peragallo - Syvertsen, Erik E. (Polar Biology, 1985)
The resting spore morphology of the antarctic diatoms Coscinodiscus furcatus Karsten and Thalassiosira australis Peragallo are described. Both species form endogenous resting spores. The spore valve of C. furcatus differ from those of the vegetative cells primarily by (i) a greater convexity and (ii) a coarser and more distinctly fasciculated areolation. This resting spore is identical to the diatom traditionally identified as C. stellaris var. symbolophorus (Grunow) Jørgensen in the Antarctic. The resting spore of T. australis differs from the vegetative cells by (i) a lack of clusters of strutted processes in a modified ring on valve face, (ii) a coarser areolation and tangential rows of areolae and (iii) a narrower and more simply structured girdle. The resting spore valve of T. australis has been described as belonging to a separate species, Actinocyclus excentricus Peragallo.
Keywords: Sørishavet; diatomeer; marinbiologi

Moderne hvalfangst. Fra provinsnæring til internasjonal storindustri - Wexelsen, Einar; Møller, Vilhelm (Sandar : grend og gård 1850-1970, med tidsbilder fra næringsliv og kulturhistorie, 1985)
Keywords: Sørishavet; Vestfold; hvalfangere; hvalfangstindustri; hvalindustri; kulturhistorie; pelagisk

Size Frequency Pattern of Euphausia Superba in the Antarctic Peninsula Waters in the Austral Summer of 1983 - Fevolden, Svein Erik; George, Robert Y. (Journal of Crustacean Biology, 1984)
In the austral summer of 1983, schools of krill from Bransfield Strait and Palmer Archipelago were analyzed for composition in terms of size frequencies and maturity stages. Juveniles dominated in all schools, and mature animals never exceeded 6.8% of the animals at any sampling site. Gravid females were encountered in only four out of 15 schools and were never more frequent than 1.8% of the animals in any school. Among subadults and juveniles the largest animals were found on the inside of Palmer Archipelago. Smaller nonreproductive animals were on the outside and in Bransfield Strait. A second group of juveniles, in a size range of 12-15 mm, was more pronounced north of Crocker Passage than south of the Passage. Their potential origin from a more slowly growing and later spawning Southern Weddell Sea population is discussed. Lack of reproductive animals in the Bransfield/South Shetlands vicinity may reflect yearly variation in this region. A hypothesis is put forward on the basis of this study that Palmer Archipelago is a nursery ground for krill spawned elsewhere. The sites of origin of this krill could be ascertained on the basis of studies of enzyme polymorphism in these populations.
Keywords: Sørishavet; Weddellhavet; krepsdyr; krill; marin biologi; plankton

Factors Governing Pelagic Production in Polar Oceans - Sakshaug, Egil; Holm-Hansen, Osmund (Marine Phytoplankton and Productivity: Proceedings of the invited lectures to a symposium organized within the 5th conference of the European Society for Comparative Physiology and Biochemistry — Taormina, Sicily, Italy, September 5–8, 1983, 1984)
Keywords: Sørishavet; fytoplankton; havis; krill; planteplankton; primærproduksjon; sjøis; sjøvann

Ti nye år: Vestfold Historielag 60 år - Thoresen, Per (Vestfoldminne, 1984)
Keywords: Sørishavet; hvalfangst; kulturhistorie; pelagisk

Hvorfor gikk det så greitt? Om nedleggelsen av hvalfangstnæringen i Vestfold - Vik, Kjell (Vestfoldminne, 1984)
Keywords: Sørishavet; Vestfold; historie; hvalfangere; hvalfangstindustri; hvalindustri; næring; pelagisk; sjøfolk; økonomi

Eventyret om hvalfangsten - Christensen, Nils Steen; Hagelund, Olav (Stokke bygdebok, 1983)
Keywords: Nordmenn; Sørishavet; Vestfold; arbeidsforhold; hvalfangere; hvalfangst; pelagisk

The antarctic diatoms Thalassiosira dichotomica (Kozlova) comb. nov. and T. ambigua kozlova - Fryxell, Greta A.; Hasle, Grethe Rytter (Polar Biology, 1983)
Two small antarctic diatoms, usually missed by traditional collection methods, have been studied in light and electron microscopes. Porosira dichotomica has been transferred to Thalassiosira since its valve structure and process pattern agree better with that genus. T. dichotomica is unusual in that some lines of areola walls are extended, sail-like, out from the valve, supporting Kozlova's original drawings. T. ambigua, the smaller of the two, has many similarities in structure with T. dichotomica, but has granules on the margin, lacks the sail-like structures on the valve, and has minor differences in processes and areola size. Bands stay together in T. ambigua and show more fine structure than many species in the genus.
Keywords: Sørishavet; diatomeer; marin biologi; oseanografi

Hvalfangstviser i Vestfold - Gjerde, Øystein; Devig, Thor N; Glette, Kåre (Eik lærerhøgskole, 1983)
Keywords: Sørishavet; Vestfold; hvalfangstindustri; hvalfangstselskaper; hvalfangstviser; hvalindustri; pelagisk

Sandefjords historie - sett gjennem Sandefjords blads spalter - Hoffstad, Arne; Berg, Knut (Sandefjords blad og trykkeri, 1983)
Keywords: Norge; Sørishavet; Vestfold; byhistorie; hvalfangere; hvalfangerselskapet; hvalfangstindustri; hvalindustri

The response of Antarctic icebergs to ocean waves - Wadhams, Peter; Kristensen, Monica; Orheim, Olav (Journal of Geophysical Research: Oceans, 1983)
The heave, tilt, and strain responses of three Antarctic tabular icebergs to ocean waves were measured during a 1980–1981 cruise of HMS Endurance to the South Atlantic. The three icebergs, located near the South Sandwich and South Orkney islands, were instrumented with accelerometers, tiltmeters, and wire strainmeters, while a Waverider buoy was used to record the ocean wave field. The thickness of the icebergs was surveyed by a helicopter-borne radio echo sounder. The heave response occurred mainly at the swell period but with outbreaks of bobbing which lasted for a few cycles at a resonant period (about 40 s), which agreed well with the predictions of a numerical finite element model. The roll response occurred mainly at a long resonant period (40–50 s), which again agreed well with the model, but there was also a significant response at ocean wave periods (5–20 s), which exceeded predictions. The strain response had a component at very long periods, which is unexplained by theory, while the surface strain at ocean wave periods agreed with the simple analytical model of Goodman et al. (1980). Using this model it is possible to predict a wave height and period that will cause breakup of the icebergs, and we conclude that swell-induced breakup is likely to occur during major storms in the open southern ocean.
Keywords: Sør-Orknøyene; Sørishavet; brehylle; geofysikk; glasiologi; havbølger; isberg; isbreer; isbrem; isfjell; isshelf; oseanografi

Technological change in the Norwegian whaling industry: A case-study in the use of patent-statistics as a technology indicator - Basberg, Bjørn L (Research Policy, 1982)
This paper presents an example of the use of patent statistics as a technology indicator in one industry. The first part deals with the problem of interpretation. Through examination of several other partial technology indicators, it is concluded that at least in this industry, patent statistics provide a reliable indicator, not only for the timing of inventions, but for the timing of innovations and diffusion as well. The reason is that the intervals between the stages in the innovation process are very short. This contradicts evidence from many other industries, and it is therefore emphasized that generalizations are unwarranted. The second part of this paper deals with the possible causes of technological change in Norwegian whaling. The methodology is inspired by J. Schmookler's work. Thus, the patents are correlated with other indicators of economic development in the industry. But while Schmookler's view is that the patent activity is determined by social demand and economic growth, the conclusions for the Norwegian whaling industry point in the opposite direction: the technological transformation that took place during the 1920s and early 1930s was forced upon the firms in their efforts to cut costs, which was achieved by rationalizing production and catching methods in line with a downward price trend for whale oil.
Keywords: Norge; Sørishavet; hvalfangst; pelagisk; teknologi; økonomi

Hvalbåten gjennom 100 år - Devig, Thor N (Vestfoldminne, 1982)
Keywords: Norge; Sørishavet; Vestfold; båter; hvalfangere; hvalfangstindustri; hvalindustri; lokalhistorie

Norge i polarområdene - Egeland, Knut (Leif Holtedahls forl., 1982)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

Biokjemiske studier over antarktisk krill - Ellingsen, Trond E; Norges tekniske høgskole Institutt for teknisk, biokjemi (Institutt for teknisk biokjemi, 1982)
Keywords: Bouvetøya; Sørishavet; Weddellhavet; biokjemi; krill; lipider; lyskreps; marinbiologi

Eventyret Anders Jahre - Jacobsen, Alf R (Oktober, 1982)
Keywords: Sørishavet; biografier; historie; hvalfangstindustri; hvalfangstselskaper; hvalindustri; pelagisk; rederier; skipsfart

Krill: mat i mengder i Sørishavet - Sakshaug, Egil (Syn og segn, 1982)
Keywords: Sørishavet; krill; marinbiologi

Evidence for a late Wisconsin glaciation of the Weddell Sea - Elverhøi, Anders (Nature, 1981)
Keywords: Sørishavet; Weddellhavet; forskning; glasiologi; sedimentologi; stratigrafi

Glaciomarine sediments and suspended particulate matter, Weddell sea, Antarctica (abstract only) - Elverhøi, Anders; Roaldset, Elen (Annals of Glaciology, 1981)
Samples of glaciomarine sediments and suspended particulate matter filtered from sea-water were collected in the Weddell Sea during the Norwegian Antarctic Research Expedition (NARE) in 1978–79. Analyses have provided information on the textural and mineralogical composition of shelf sediments, on the nature of biogenic and inorganic suspended particulate matter, and on the total sediment transport to the shelf areas and further into the deeper waters (). The shelf waters contain 0.1 to 1.2 g m–3 of suspended particulate matter, which is close to the range of 0.5 to 1.5 g m–3 reported for suspension concentrations in the oceans, but considerably lower than that found for some other glaciomarine environments such as the Bering Sea {up to 13-15 g m–3 ()) and off Kongsbreen, Spitsbergen {up to 500 g m–3 ()). Suspended particles from the Weddell Sea have maximum sizes of 50 to 70 µm and mean diameters in the range of 10 to 20 µm. In contrast, the bottom sediments on the outer shelf are deficient in the corresponding fractions. This reflects that when floating Antarctic ice supplies material to the Weddell Sea, the coarser fragments (>20-70 µm) are deposited, while the medium silt and finer fractions go into suspension. Considering the suspended-load data and the bottom-current measurements on the shelf break, it is evident that in January 1979 an average of 8.6 × 104tonnes d–1 (or 32 × 106 tonnes a–l) of particulate matter was transported by the current from the central Weddell Sea to the South Atlantic deep water. Morphological (scanning electron microscopy) and chemical analyses show the suspended material to be dominated by silica organisms (diatoms), and also to contain clastic grains of phyllosilicates, feldspar, quartz, zircon, in a few cases Al- and Fe-hydroxides/oxides also; authigenic “Fe-sepiolite” and secondary gypsum. Mineralogical analyses (X-ray diffraction) of the bottom sediments show the fine sand silt fractions to contain mainly clastic materials like illite, smectite-vermiculite, and quartz. Biogenic silica (cristobalite) and carbonate (Mg-calcite) as well as authigenic Fe-silicates (“Fe-sepiolite”) are also present.
Keywords: Sørishavet; glasiologi; sedimenter

Enzyme polymorphism in Antarctic krill (Euphausiacea); genetic variation between populations and species - Fevolden, Svein Erik; Ayala, Fransisco J. (Sarsia, 1981)
By means of enzyme electrophoretical assays three samples of Euphausia superba, all from the Atlantic sector of the Antarctic Ocean, were examined to see whether or not they represent genetically separated populations. The same samples were also compared with E. superba from off the Western coast of the Antarctic Peninsula, representing the Pacific sector. The latter animals have previously been studied by other authors. One sample of a second species of Antarctic krill, E. crystallorophias, was likewise examined. Thirty-five loci were studied in E. superba, and it is concluded that the three samples from the Atlantic sector most probably do not represent reproductively isolated populations. Their average heterozygosity, about 10%, is however greater than the value previously found for the ‘Pacific’ E. superba, 5.8 %. Calculations of the genetic identity and genetic distance between the Atlantic and ‘Pacific’ samples of E. superba suggest they represent separate populations. The average heterozygosity of E. crystallorophias was estimated to be between 9.1 and 9.4 %, from studies of 33 loci. The genetic distance between this species and E. superba was estimated at 0.989. The results are finally discussed in terms of postulated theories on genetic variability versus environmental heterogeneity.
Keywords: NARE 1976/77; NARE 1978/79; Sørishavet; genetikk; krill; marin biologi; plankton

Bacteriologigal characteristics of Antarctic krill (Crustacea, Euphausiacea) - Fevolden, Svein Erik; Eidså, Gudmunn (Sarsia, 1981)
The bacterial flora of two species of Antarctic krill, Euphausia superba Dana and E. crystallorophias Holt & Tattersall, was studied with the aim of investigating the role played by bacteria during the claimed rapid deterioration of these animals. The number of bacteria on fresh krill was characterized as low, but started to increase exponentially after a few days of storage at low temperatures. Dominant species were of the genera Moraxella, Pseudomonas, and Alteromonas. Comparing the low initial number of bacteria with the high autolytic activity it is suggested that the rapid degradation of krill during the first days of storage is induced by autolysis and not by bacterial activity.
Keywords: Sørishavet; biokjemi; krill; lyskreps; marin biologi; plankton

Hydrographic and current measurements in the southern Weddell Sea 1979/80 - Gammelsrød, Tor; Slotsvik, Noralf (Polarforschung, 1981)
During the 1979-1980 expediton with the icebreaker Polarsirkel we had an excellent opportunity to study the physical oceanography of the inner part of the Weddell Sea. The ship followed the ice shelf barrier from Cape Norwegia at about 15 °W, and due to favourable ice conditions, it was able to penetrate all the way to the Antarctic Peninsula (60 0W). In this preliminary report we give a review of the physical oceanography programme which mostly consists of hydrographic (CTD) stations near the barrier, and also sorne current and water level measurernents. The different water masses observed are described and the possibility for a tidal-drlvcn upwelling near the ice shelf barrier is indicated.
Keywords: AABW; Sørishavet; Weddellhavet; bunnvannet; havis; hydrografi; isshelf; oseanografi; sjøis; sjøvann; vannmasser

Hvalfangst 1868-1914. Hvalfangst blir en ny vekstnæring - Hodne, Fritz (Norges økonomiske historie 1815-1970, 1981)
Keywords: Norge; Sørishavet; historie; hvalfangere; hvalfangstindustri; hvalindustri; økonomi

Morphology of the Weddell Sea and southwest Indian Ocean - Johnson, G Leonard; Vanney, Jean-René; Elverhøi, Anders; LaBrecque, John L (Deutsche Hydrografische Zeitschrift, 1981)
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; forskning; geologi; havbunnen; tektonikk

Shipping - mitt liv : en selvbiografi - Næss, Erling Dekke; Cameron, Eric (A/S Hjemmet Fagpresseforlaget, 1981)
Keywords: Sørishavet; biografier; hvalfangere; hvalfangst; sjøfart; skippere; skipsfart

Blåhvalen, kan de reddes? - Smelror, Morten (Naturen, 1981)
Keywords: Sørishavet; hvaler; hvalfangst

Hvalfangerne forteller. Innsammlig av hvalfangstens tradisjonsmateriale i Vestfold - Wexelsen, Einar; Devig, Thor N (Vestfoldminne, 1981)
Keywords: Sørishavet; Vestfold; erindringer; historie; hvalfangere; hvalfangst; hvalfangstnæring; pelagisk

Konvensjon om bevaring av marine levende ressurser i Antarktis = Convention on the Conservation of Antarctic Marine Living Resources (Lovdata, 1980)
Keywords: Sørishavet; forvaltning; jus; marinbiologi; miljøvern; naturvern

Flow Around Icebergs - Foldvik, Arne; Gammelsrød, Tor; Gjessing, Yngvar (Annals of Glaciology, 1980)
Keywords: NARE 1978/79; Sørishavet; Weddellhavet; glasiologi; isberg; observasjoner; oseanografi; sjøvann

Hvalfangst i Sørishavet - Pedersen, Arne Fevang (Kampen på havet : en krigsseilers beretning, 1980)
Keywords: Sørishavet; biografier; erindringer; historie; hvalfangere; hvalfangst; pelagisk

Some satellite tracked iceberg drifts in the Antarctic - Vinje, Torgny E (Annals of Glaciology, 1980)
Keywords: Sørishavet; drivis; havis; isberg; isdrift; isfjell; oseanografi; sjøis; vannmasser

Investigations on krill (Euphausiacea) sampled during the Norwegian Antarctic Research Expedition 1976–1977 - Fevolden, Svein Erik (Sarsia, 1979)
Krill was sampled in the Weddell Sea, farther south than ever before, and off Bouvet-öya. Five species were found: Euphausia superba, E. crystallorophias, E. frigida, E. triacantha, and Thysanoessa macrura. E. superba and E. crystallorophias were the most abundant species north and south of 74° S respectively. Length frequency analyses suggest that E. superba from the inner Weddell Sea takes three years to reach maturity. This population differed in several aspects from the populations farther north. E. crystallorophias and T. macrura were registered south to 77°45′ S, the southernmost localisation investigated. The material gives no clear evidence whether these species take one or two years to reach maturity. Their spawning activity seems to start earlier in the season than for E. superba. E. frigida and E. triacantha were only-found off Bouvetöya. Continuous echosounder recordings revealed that the total abundance of krill in the southern parts of the Weddell Sea was low, as was also the abundance on the route between the South Orkney Islands and Dronning Maud Land.
Keywords: Bouvetøya; Dronning Maud Land; NARE 1976/77; Sør-Orknøyene; Sørishavet; Weddellhavet; dyreplankton; krill; plankton; zooplankton

The genus Thalassiosira: species with internal extensions of the strutted processes - Fryxell, Greta A; Hasle, Grethe Rytter (Phycologia, 1979)
Keywords: Sørishavet; diatomeer; marinbiologi; oseanografi

Melting of ice in sea water: a primitive model with application to the Antarctic ice shelf and ice bergs - Gade, Herman G. (University of Bergen, Geophysical Institute. Report, 1978)
Keywords: Sørishavet; havis; oseanografi

Hvalmål. Om lengden på blåhvalhunner fanget av norske selskaper i Antarktis - Bragstad, Torunnn (Sandefjordmuseene. Årbok, 1976)
Keywords: Sørishavet; historie; hvalfangere; hvalfangstselskaper; hvalindustri

The biogeography of some marine planktonic diatoms - Hasle, Grethe Rytter (Deep Sea Research and Oceanographic Abstracts, 1976)
Keywords: Sørishavet; biogeografi; ekspedisjoner; forskning; fytoplankton; marinbiologi; plankton; planteplankton

Sandefjord - byen vår : trekk fra Sandefjordsdistriktets historie under hvalfangsteventyret 1905-1968 - Hoffstad, Arne ([S.n.], 1976)
Keywords: Norge; Sørishavet; Vestfold; byhistorie; hvalfangere; hvalfangerselskapet; hvalfangstindustri; hvalfangstselskapet; hvalindustri

Smia på Fevang - Thoresen, Per (Vestfoldminne, 1976)
Keywords: Nordmenn; Sørishavet; erindringer; hvalfangere; hvalfangst; pelagisk

På hvalfangst med Salvesen - Asplin, Tore (T. Asplin, 1974)
Keywords: Nordmenn; Sørishavet; erindringer; fortellinger; historie; hvalfangere; hvalfangst; pelagisk

Conditional instability of sea water at the freezing point - Foldvik, Arne; Kvinge, Thor (Deep Sea Research and Oceanographic Abstracts, 1974)
Keywords: AABW; Sørishavet; bunnvannet; havis; oseanografi; sjøis; sjøvann

Internasjonale konferanser - Hva har de ført til? - Kyst-Norge], [Aksjon; Brox, Ottar (Kampen om havet, 1974)
Keywords: Sørishavet; havrett; hvalfangst; hvalfangstkvoten; internasjonal; jus; pelagisk; politikk

Hvalfangsforhandlingene i historisk og prinsipielt perspektiv: økonomi, biologi, politikk - Midgaard, Knut (Forskningspolitiske spørsmål i norsk biologi : en seminarrapport = Policy issues in Norwegian biological research : report from a seminar, 1974)
I. Vi skal i det følgende beskjeftige oss med forhandlingene om regulering av den pelagiske hvalfangst i Antarktis med sikte på å belyse to emner: 1) betingelsene for at biologers premisser skal slå igjennom i en politisk prosess som gjelder utnyttelsen av levende ressurser, 2) rollekonflikter som kan oppstå for biologer som går inn i en slik prosess. Jeg vil først gi en historikk, og så gå nærmere inn på de to emnene.
Keywords: Den internasjonale hvalfangstkommisjonen; Norge; Sørishavet; hvalfangstkonvensjonen; hvalfangstkvoter; internasjonal politikk; pelagisk hvalfangst

Retrieval of current meters and study of thermohaline convection in the Weddell Sea - Bø, Redair; Foldvik, Arne; Kvinge, Thor (Antarctic Journal of the United States, 1973)
Keywords: Sørishavet; Weddellhavet; geofysikk; oseanografi

Bergens deltakelse i den moderne hvalfangst - Tønnessen, Johan Nicolay (Sjøfartshistorisk årbok : Norwegian yearbook of maritime history, 1973)
Keywords: Antarktis; Sørishavet; historie; hvalfangstindustri; hvalfangstselskaper; hvalindustri; skipsfart

Hvalfangstens historie - Tønnessen, Johan Nicolay; Solhaug, Trygve (Historisk tidsskrift, 1973)
Keywords: Sørishavet; bokanmeldelser; historie; hvalfangst; pelagisk

Sperm whales of the southeast pacific. Part III : Norphometry - Clarke, Robert; Paliza, Obla (Universitetsforlaget, 1972)
Keywords: Sørishavet; forskning; hvaler; marin biologi; oseanografi

Joh. N. Tønnessen: Den moderne hvalfangst historie. Opprinelse og utvikling. Bind 2-4. Utgitt av Norges hvalfangstforbund, Sandefjord 1967, 1969, 1970. - Solhaug, Trygve (Historisk tidsskrift, 1972)
Keywords: Sørishavet; bokanmeldelser; historie; hvalfangst; pelagisk

Corethron Criophilum Castracane: Its distribution and structure - Fryxell, Greta A; Hasle, Grethe Rytter (Biology of the Antarctic Seas IV, 1971)
Keywords: Sørishavet; fytoplankton; marinbiologi; plankton; planteplankton

Morphologic Variability in Fasciculated Diatoms as Exemplified by Thalassiosira Tumida (Janisch) Hasle, Comb. Nov - Hasle, Grethe Rytter; Heimdal, Berit R; Fryxell, Greta A (Biology of the Antarctic Seas IV, 1971)
Keywords: Sørishavet; Weddellhavet; alger; marinbiologi; oseanografi; plankton

Diatoms: Cleaning and Mounting for Light and Electron Microscopy - Hasle, Grethe R; Fryxell, Greta A (Transactions of the American Microscopical Society, 1970)
Keywords: Sørishavet; Weddellhavet; diatomeer; marinbiologi; oseanografi

Den pelagiske fangst : 1937-1969 - Tønnessen, Johan Nicolay (Norges Hvalfangstforbund, 1970)
Keywords: Norge; Sørishavet; fangst; historikk; husholdning; hvalfangst; hvalfangstkvoten; landbruk; pelagisk

"Cutty Shark" i hvalfangsten tjeneste - Berg, Knut (Årbok. Sandefjord bymuseum, 1969)
Keywords: Sørishavet; historie; hvalbåter; hvalfangere; hvalfangstindustri; hvalindustri; pelagisk; skip

An analysis of the phytoplankton of the Pacific Southern Ocean: abundance, composition, and distribution during the Brategg Expedition, 1947-1948 - Hasle, Grethe Rytter (Universitetsforlaget, 1969)
Keywords: Brategg ekspedisjon; Sørishavet; ekspedisjoner; forskning; fytoplankton; marinbiologi; plankton; planteplankton

"Forlandet" ex "Femern" ex "Foca" - Knap, Johan (Årbok. Sandefjord bymuseum, 1969)
Keywords: Sørishavet; historie; hvalbåter; hvalfangere; hvalfangstindustri; hvalindustri; pelagisk; skip

Verdensfangsten 1883-1924 : Del II 1914-1924 - Tønnessen, Johan Nicolay (Norges Hvalfangstforbund, 1969)
Keywords: Norge; Sørishavet; fangst; historikk; husholdning; hvalfangst; hvalfangstkvoten; landbruk; pelagisk

The distribution of zooplankton in the southern ocean and its dependence on the circulation of water - Voronina, N. M. (Sarsia, 1968)
The distribution of zooplankton in the Southern Ocean depends on seasonal changes in quantity and on redistribution of the plankton by currents. In the upper 100 m the meridianal component of the current shifts the maxima of some species northwards from the divergence zone at a mean velocity of about 20 cm/sec. In the Antarctic convergence zone the water sinks at a mean velocity of 10.5 m/day. This brings about an increase of the total plankton amounting to about 3% per day. As the southward flow of deep water is very slow the transfer of plankton in this layer is negligible.
Keywords: Sørishavet; marin biologi; oseanografi; plankton

Sperm whales of the Southeast Pacific. Part I: Introduction. Part II: Size range, external characters and teeth - Clarke, Robert; Anelio, Aguayo L; Obla, Paliza (Universitetsforlaget, 1968)
Keywords: Sørishavet; forskning; hvaler; marin biologi; oseanografi

Morphology and distribution of the marine centric diatom Thalassiosira antarctica Comber - Hasle, Grethe R; Heimdal, Berit R (Journal of the Royal Microscopical Society, 1968)
Keywords: Sørishavet; diatomeer; fytoplankton; marinbiologi; plankton

Hvalfangst - Wasberg, Gunnar Christie (red.) (Sandar bygdebok, 1968)
Keywords: Sørishavet; Vestfold; historie; hvalfangere; hvalfangstindustri; hvalindustri; pelagisk

Verdensfangsten 1883-1924. Del I : 1883-1914 - Tønnessen, Johan Nicolay (Norges Hvalfangstforbund, 1967)
Keywords: Norge; Sørishavet; fangst; historikk; husholdning; hvalfangst; hvalfangstkvoten; landbruk; pelagisk

Nitzschia and Fragilariopsis species studied in the light and electron microscopes: 2. The group Pseudonitzschia - Hasle, Grethe Rytter (Universitetsforlaget, 1965)
Keywords: Sørishavet; alger; diatomeer; kiselalger; marinbiologi

Nitzschia and Fragilariopsis species studied in the light and electron microscopes: 3. The genus Fragilariopsis - Hasle, Grethe Rytter (Universitetsforlaget, 1965)
Keywords: Sørishavet; alger; diatomeer; kiselalger; marinbiologi

"Pelagos" ex "Athenic" - Berg, Knut (Vestfold-minne, 1964)
Keywords: Sørishavet; historie; hvalbåter; hvalfangerflåte; hvalfangstindustri; hvalfangstselskaper; hvalindustri; pelagisk

Folketro på hvalfangst - Eriksen, Erling (Vestfold-minne, 1964)
Keywords: Sørishavet; erindringer; fortellinger; historie; hvalfangere; hvalfangst; pelagisk; sjøfolk

Hvalfangsten - Gjermoe, Eilif (Aksjekursene i norsk skipsfart, skipsbygging og hvalfangst i mellomkrigstiden, 1964)
Keywords: Antarktis; Sørishavet; historie; hvalfangst; næringsliv; økonomi

Sydishavet og tilgrensende områder: Blad 11 - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1964)
Keywords: Norsel (skip); Sørishavet; geografi; kartlegging

Nitzschia and Fragilariopsis species studied in the light and electron microscopes. 1. Some marine species of the groups Nitzschiella and Lanceolatae - Hasle, Grethe Rytter (Universitetsforlaget, 1964)
Keywords: Sørishavet; alger; diatomeer; kiselalger; marin biologi

Noen problemer i den moderne hvalfangsts historie - Tønnessen, Johan Nicolay (Vestfold-minne, 1964)
Keywords: Carl Anton Larsen; Henrik Johan Bull; Svend Foyn; Sørishavet; historie; hvalfangstindustri; hvalfangstselskaper; hvalindustri; næring; pelagisk; polareksspedisjoner; økonomi

Den moderne hvalfangst - Weyergang-Nielsen, Arthur (Larviks historie, 1963)
Keywords: Sørishavet; historie; hvalfangst; pelagisk

Hvalfangst - Weyergang-Nielsen, Arthur (Larviks historie, 1963)
Keywords: Nordmenn; Sørishavet; Vestfold; historie; hvalfangere; hvalindustri; pelagisk

Development of tooth germs and adjacent structures in the whalebone whale (Balaenoptera physalus (L.)) - Karlsen, Kjell (Universitetsforlaget, 1962)
Keywords: Sørishavet; forskning; hvaler; marin biologi

Benthonic problems in Antarctic and Arctic waters - Broch, Hjalmar (Aschehoug, 1961)
Keywords: Norvegia ekspedisjoner; Sørishavet; marin biologi; polarområdene; zoogeografi

Tønsbergs sjøfart gjennom 100 år - Eriksen, Erling (Vestfoldminne, 1961)
Keywords: Sørishavet; Vestfold; historie; hvalfangstindustri; hvalkokerier; pelagisk; skipsbyggerier

Oversiktskatalog 1 : over bøker, periodiske skrifter og særtrykk ved Hvalfangstmuseets bibliotek - Fjeld-Andersen, Asbjørn (Hvalfangstmuseum, 1961)
Keywords: Antarktis; Sørishavet; bibliografi; hvalfangst; litteratur; pelagisk

Hvalfangstens utvikling og dens hovedproblem i dag - Bettum, Frithjof (Norges handelshøyskole, 1960)
Keywords: Sørishavet; historie; hvalfangst; politikk

Sandar sparebank gjennom 100 år : utgitt ved hundre års jubileet - Laug, Kristian ([s.n.], 1960)
Keywords: Antarktis; Norge; Sørishavet; Vestfold; hvalfangstindustri; hvalindustri; økonomi

Vestfold rederiforening gjennom 50 år : 1909-1959 - Eriksen, Erling (Foreningen, 1959)
Keywords: Norge; Sørishavet; Vestfold; historie; hvalbåter; hvalfangere; hvalfangstindustri; hvalfangstselskaper; hvalindustri; pelagisk; rederier

Vestfold rederiforening gjennom 50 år : 1909-1959 - Eriksen, Erling (Foreningen, 1959)
Keywords: Sørishavet; Vestfold; hvalbåter; hvalfangstindustri; pelagisk; rederier

Et hvalfangerbrev - Larsen, Tryggen (Magasinet for alle, 1959)
Keywords: Sørishavet; hvalfangst

Femti år i konkurranse og fremgang : aktieselskapet Tønsbergs Hvalfangeri 1907-1957 - Wasberg, Gunnar Christie (Tønsbergs Hvalfangeri. Styret, 1958)
Keywords: Nordmenn; Norge; Sørishavet; historie; hvalfangere; hvalfangstindustri; hvalfangstselskaper; hvalindustri; pelagisk

Banken og byen : Sandefjords sparebank 1857-1957 - Groth, Erling (Sandefjords sparebank, 1957)
Keywords: Norge; Sørishavet; Vestfold; byhistorie; hvalfangere; hvalfangerselskapet; hvalfangstindustri; hvalfangstselskapet; hvalindustri; økonomi

Pacific Antarctic waters - Midttun, Lars; Natvig, Johan (Hvalfangstmuseet, 1957)
Keywords: Brategg ekspedisjon; Sørishavet; havbunnen; hydrografi; oseanografi; vannmasser

Phytoplankton and Hydrography of the Pacific Part of the Antarctic Ocean - Hasle, Grethe Rytter (Nature, 1956)
Keywords: Sørishavet; fytoplankton; hydrografi

Hvalfangerne og hvalfangsten - Hjertholm, Sverre (Arbeiderbevegelsen i Vestfold : trekk fra den politiske og faglige arbeiderbevegelse 1906-1956, 1956)
Keywords: Norge; Sørishavet; Vestfold; arbeiderbevegelse; hvalfangere; hvalfangstindustri; hvalindustri

Internasjonal regulering av hvalfangsten: et tilbakeblikk og en vurdering - Ruud, Johan T (Samtiden, 1956)
Keywords: Sørishavet; forvaltning; historie; hvalfangst; politikk

Researches into the prevalence of trichinosis in animals in arctic and antarctic waters - Thorshaug, K.; Rosted, A. Fr. (Brøggers forlag, 1956)
Keywords: Sørishavet; biologi; dyr; parasitter

70 år : Lars Christensen og hans samtid - Bogen, Hans (Tanum, 1955)
Keywords: Lars Christensen; Sørishavet; biografi; historie; hvalfangere; hvalfangst

Whaling - Petersen, Kaare (The saga of Norwegian shipping : an outline of the history, growth and development of a modern merchant marine, 1955)
Keywords: Norge; Sørishavet; historie; hvalbåter; hvalfangst; pelagisk; sjøfart; skipsfart

Norske rederier gjennom 50 år - Sethne, Hans (Red.); Hauge, Eiliv Odde (Sverre Kildahls Boktr., 1955)
Keywords: Norge; Sørishavet; historie; hvalfangstindustri; hvalindustri; rederier; skipsfart

Nitti års norsk hvalfangst - Bogen, Hans (Norge på havet, 1954)
Keywords: Roald Amundsen; Sydpolsekspedisjonen; Sørishavet; historie; hvalfangere; hvalfangstindustri; hvalfangstselskaper; hvalindustri; pelagisk; skipsfart

Sandefjord og Sandar de siste 30 år - Lind, Ole (Sandefjord kommunale handelsgymnasium og handelsskole : 1904-1954, 1954)
Keywords: Sørishavet; Vestfold; byhistorie; hvalfangere; hvalfangstindustri; hvalindustri

Norges skibsførere : 1935-1953 - Meling, Torjer (red.); Berg, Gabriel (red.); Bjønness, Henry (red.); Lindtner, N Fr. (red.) (Dreyer, 1954)
Keywords: Nordmenn; Sørishavet; biografier; historie; hvalfangere; hvalfangst; pelagisk; sjøfolk; skipsfart; skipsførere

Hval og mannfolk - Robertson, R B; Stai, Arne (Gyldendal, 1954)
Keywords: Nordmenn; Sørishavet; ekspedisjon; hvalfangere; hvalfangst; pelagisk; sjøfolk

Tidal currents off the antarctic ice barrier, Queen Maud Land - Sverdrup, Harald Ulrik (Archiv für Meteorologie, Geophysik und Bioklimatologie, Serie A, 1954)
Observations of tidal currents in lat. 71° 01′ S, long. 10° 55′ W indicate that a semi-diurnal tidal wave progresses towards the WSW, that is, parallel to the main direction of the barrier. ForM2 the cotidal hour appears to be about 7h, in good agreement with the value 6.7h, that is derived from observations of the atmospheric pressure. Furthermore, the current measurements indicate that the ratio(K1+O1)/(M2+S2) is large, perhaps as large as 2.5.
Keywords: Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; Sørishavet; havstrømmer; klimaendringer; meteorologi; oseanografi; tidevann

Speiderguttene som drog på hvalfangst - Amundsen, Sverre S (Aschehoug, 1953)
Keywords: Nordmenn; Sørishavet; fortellinger; hvalfangere; hvalfangst

Aktieselskabet "Ørnen" 10/1 1903 - 10/1 1953 : 50 års hvalfangst - Bogen, Hans (A/S "Ørnen", 1953)
Keywords: Norge; Sørishavet; hvalfangstindustri; hvalfangstselskaper; hvalindustri

Privatbanken i Sandefjord A/S : 10-12-1928 - 10-12-1953 : spredte trekk til privatbankvesenets historie i Sandefjord - Bogen, Hans (Utgitt av Privatbanken i Sandefjord A/S, 1953)
Keywords: Forretningsbanker; Historie; Norge; Sørishavet; hvalfangst; hvalfangstindustri; hvalindustri

Hvalfangerselskapet "Pelagos" A/S 1928 - 30.juni - 1953 : et tilbakeblikk - Bruun, Svend Foyn (Tønsbergs Aktietrykkeri, 1953)
Keywords: Sørishavet; festskrifter; hvalbåter; hvalfangstindustri; hvalfangstselskap; hvalindustri; hvalkokerier; pelagisk; skip

Studies on the cetacean brain : the gross anatomy of the rhombencephalon of the fin whale <Balaenoptera physalus L.> - Jansen, Jan (I kommisjon hos Dybwad, 1953)
Keywords: Sørishavet; forskning; hvaler; marin biologi

Harpuner og mannfolk : fra en fangstferd i Antarktis - Ree, Ørnulf (A.S Sæbbøs, 1953)
Keywords: Sørishavet; geografi; historie; hvalfangere; hvalfangst

On Conditions for the Vernal Blooming of Phytoplankton - Sverdrup, Harald Ulrik (ICES Journal of Marine Science, 1953)
Keywords: Sørishavet; forskning; oseanografi; planteplankton

Aksjeselskapet Kosmos gjennom 25 år : en epoke i Antarktis - Thorson, Odd (Dreyer, 1953)
Keywords: Sørishavet; historie; hvalfangstselskaper; hvalindustri; næringslivet; skipsfart; skipsredere

Whaling - Paulsen, Harald B (Industries of Norway : technical and commercial achievements, 1952)
Keywords: Sørishavet; hvalfangstindustri; næringsliv; pelagisk

Investigations on the anterior lobe of the hypophysis of the finback whale (B. Physalus L.) - Sverdrup, Arne; Arnesen, Kristen (I kommisjon hos Dybwad, 1952)
Keywords: Sørishavet; forskning; hvaler; marin biologi

Fem hundre år og femti : fra tollsted til ladested : fra badeby til hvalfangst-sentrum : linjer i Sandefjords økonomiske historie gjennem 550 år - Bogen, Hans (Sandefjord handelsstands forening, 1951)
Keywords: Sørishavet; historie; hvalfangere; hvalfangerselskapet; hvalfangstindustri; hvalindustri; økonomi

Sandefjord handelsstands forening 1901-1951. Bilag til Hans Bogens jubileumsbok "Femhundre år - og femti" - Bogen, Hans; Schelbred, Erik W; Bøe, Frithjof; Klungseth, Alf; Schelbred, Oscar C; Sandberg, Finn; Fogstad, Per; Vangstein, Einar; Hoffstad, Arne (Sandefjord handelsstands forening, 1951)
Keywords: Sørishavet; historie; hvalfangere; hvalfangerselskapet; hvalfangstindustri; hvalindustri; økonomi

Loggbok blant hvalfangere : med norske hvalfangere i Antarktis - Boldt-Christmas, G E F; Johnsen, Gunnar (Handelstrykkeriets Forlag, 1951)
Keywords: Sørishavet; dagbok; erindringer; historie; hvalfangere; hvalfangstindustri; pelagisk

Hval i sikte - Mielche, Hakon (Grieg, 1951)
Keywords: Sørishavet; hvalfangst

Subantarctic and Antartic fishes - Nybelin, Orvar (Hvalfangstmuseet, 1951)
Keywords: Brategg ekspedisjon; Sørishavet; ekspedisjoner; fisker; forskning; iktiogeografi; magellanstredet; zoologi

Hvalfangerselskapet Globus A/S 1925-1950 : et kapitel av den moderne hvalfangsts historie - Næss, Øyvind ([s.n.], 1951)
Keywords: Norge; Sørishavet; historie; hvalfangerselskapet; hvalfangstindustri; hvalindustri; skipsredere

Sydishavet: Blad 2 - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1950)
Keywords: Bouvetøya; Dronning Maud Land; Sørishavet; geografi; kartlegging

The insulin content of whale pancreas - Jorpes, J Erik (I kommisjon hos Dybwad, 1950)
Keywords: Sørishavet; biokjemi; forskning; hvaler; marin biologi; medisin

Blod, svette og tårer - Orud, Hilmar (Magasinet for alle, 1950)
Keywords: Sørishavet; hvalfangst

Studies in whale oils on the content of saturated fatty acids in whale oils : with a note on the content of positional isomeric hexadecenoic and octadecenoic acids in partially hardened antarctic whale oil - Pedersen, Torbjørn (I kommisjon hos Dybwad, 1950)
Keywords: Sørishavet; biokjemi; hvaler; hvalolje; kjemiske analyser; marin biologi

Age-studies on blue whales - Ruud, Johan T; Jonsgård, Åge; Ottestad, Per (I kommisjon hos Dybwad, 1950)
Keywords: Sørishavet; forskning; hvaler; marin biologi

Hvalfangerne kommer. Sammenslutningen med radiotelegrafistene. En stormakt på havet - Zachariassen, Aksel (Fra trellekår til frie menn : Norsk sjømannsforbund gjennom 40 år, 1950)
Keywords: Norge; Sørishavet; fagforeninger; historie; hvalfangere; hvalfangstindustri; hvalindustri; pelagisk; sjømenn

Kort oversikt over den norske pelagiske hvalfangst 1939-1949 - Bogen, Hans (Liv og virke ved polene : polarboken 1949, 1949)
Keywords: Sørishavet; historie; hvalfangst

Sydishavet og tilgrensende farvann: Blad 12 - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1949)
Keywords: Sørishavet; geografi; hvalfangst; kartlegging

Fangsten i nord og syd - Høeg, Ths. Arbo (Larviks sjømannsforening 1849-1949 og byens skibsfart i samme tidsrum, 1949)
Keywords: Sørishavet; Vestfold; historie; hvalfangst; hvalfangstselskaper; pelagisk

Del IV: Hvalfangst - fangstnæring - Knudtzon, Hans Thomas (Norsk fiskeri- og fangsthåndbok : saltvannsfiskeriene : ferskvannsfiskeriene : ishavsfangsten : hvalfangsten, 1949)
Keywords: Sørishavet; fiskerier; historie; hvalfangere; hvalfangst; hvalfangstindustri; hvalfangstkvoter; hvalfangstregulering; hvalfangstselskaper; hvalindustri; internasjonal; næring; pelagisk; samarbeid; økonomi

A/s Framnæs Mek. Verksted : 1898 - 1948 - Bogen, Hans (Dreyer, 1948)
Keywords: Norge; Sørishavet; Vestfold; historie; hvalfangst; hvalfangstindustri; hvalindustri; skipsbyggerier; skipsbygging; skipsverft

Some new and remarkable leeches from the Antarctic seas - Brinkmann, August (Dybwad, 1948)
Keywords: Bouvetøya; Norvegia ekspedisjonen; Sørishavet; fisker; igler; marin biologi

Studies on female fin and blue whales : report on investigations carried out in the Antarctis during the seaeon 1939-1940 - Brinkmann, August (I kommisjon hos Dybwad, 1948)
Keywords: Sørishavet; hvaler; hvalfangstindustri; hvalindustri; marin biologi; pelagisk

Vitamins in whale liver - Brækkan, Olaf R (I kommisjon hos Dybwad, 1948)
Keywords: Sørishavet; biokjemi; forskning; hvaler; marin biologi

Hvalfangst på sydfeltet i krigstiden - Vikestad, Arne (Tusen norske skip : en antologi over norske sjøfolks innsats i den annen verdenskrig, 1948)
Keywords: Nordmenn; Sørishavet; Verdenskrigen 1939-45; ekspedisjoner; erindringer; hvalbåter; hvalfangst; pelagisk

Vestfold og hvalfangsten - Bogen, Hans (Årbok for Den norske turistforening, 1947)
Keywords: Sørishavet; historie; hvalfangst; økonomi

Norwegian patents relating to whaling and the whaling industry : a statistical and historical analysis - Johnsen, Arne Odd (A. W. Brøggers Boktrykkeri A/S, 1947)
Keywords: Nordmenn; Norge; Sørishavet; harpuner; hvalfangere; hvalfangst; hvalfangstindustri; hvalindustri; patenter; pelagisk; økonomi

Sydishavet (Blad 5) - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1946)
Keywords: Sørishavet; geografi; kartlegging

Sydishavet (Blad 7) - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1946)
Keywords: Sørishavet; geografi; kartlegging

Sydishavet (Blad 8) - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1946)
Keywords: Sørishavet; geografi; kartlegging

Atlas over dele av det antarktiske kystland = Atlas of parts of the Antarctic coastal lands - Hansen, Hans Edvard; Luncke, Bernhard (Grøndahl, 1946)
Keywords: Antarktis; Lars Christensen; Sørishavet; Thorshavn ekspedisjon; flyfoto; kartlegging; luftfoto

Trekkfugl : roman fra hvalfangsten - Jensen, Otto A (Ansgar, 1946)
Keywords: Sørishavet; hvalfangst; pelagisk; skjønnlitteratur

A bibliography of whales and whaling : selected papers from the Norwegian research work 1860-1945 - Pedersen, Torbjørn (I kommisjon hos Dybwad, 1946)
Keywords: Sørishavet; bibliografi; hvaler; hvalfangstindustri; hvalindustri; litteratur; pelagisk

Fra Spitsebergisen til Sydhavsbrisen - Stavseth, Reidar (Arven fra Bjørn Farmann : Tønsberg Sjømannsforening gjennom 100 år, 1946)
Keywords: Nordmenn; Sørishavet; historie; hvalfangst; pelagisk; sjøfolk

Hvalen som råvarekilde - Thon, Eivind (Råvarene i verdenshandelen : kapitler av deres historie, og kampene om dem, 1946)
Keywords: Sørishavet; hvalfangstindustri; hvalindustri; hvalolje; økonomi

Nordmenn under Sydkorset - Mathiesen, Axel F (Gyldendal, 1945)
Keywords: Sørishavet; historie; hvalfangst

Blant isfjell og hval - Krafft, Arne (De Unges forlag, 1942)
Keywords: Sørishavet; fangst; hvalfangere; hvalfangst; pelagisk; sjøfolk

The oceans : their physics, chemistry, and general biology - Sverdrup, Harald Ulrik; Johnson, Martin W.; Fleming, Richard H. (Prentice-Hall, 1942)
Keywords: Sørishavet; marin biologi; oseanografi

Nordmennenes første jul i Sydishavet - Aagaard, Bjarne (Norge i Ishavet, 1941)
Keywords: Sørishavet; historie; hvalfangst

Pelagic whaling in the Antarctic : 9 : The season 1938-1939 - Bergersen, Birger; Ruud, Johan T (I kommisjon hos Dybwad, 1941)
Keywords: Sørishavet; hvaler; hvalfangst; pelagisk; polarområdene

Endocrinological studies in the blue whale (Balaenoptera musculus L.) - Jacobsen, Alf P. (I kommisjon hos Dybwad, 1941)
Keywords: Sørishavet; anatomi; biologi; fysiologi; hvaler; pelagisk hvalfangst

Pelagic whaling in the Antarctic : 8 : The season 1937-1938 - Bergersen, Birger; Lie, J; Ruud, Johan T (I kommisjon hos Dybwad, 1939)
Keywords: Sørishavet; hvaler; hvalfangst; pelagisk; polarområdene

Fischerei und Fang - Johnsen, Oscar Albert (Norwegische Wirtschaftsgeschichte, 1939)
Keywords: Sørishavet; hvalfangst; pelagisk; økonomi

Pelagic whaling in the Antarctic : 7 : The season 1936-1937 - Hjort, Johan; Lie, J; Ruud, Johan T; Ottestad, Per (I kommisjon hos Dybwad, 1938)
Inneholder: A preliminary report on: Variations in the size distribution of Southern blue and fin whales by Per Ottestad
Keywords: Sørishavet; hvaler; hvalfangst; pelagisk; polarområdene

Om hvalfangstens naturgrunnlag - Ruud, Johan T (Naturen, 1938)
Keywords: Sørishavet; hvaler; marinbiologi; zoologi

Med kanon og kamera efter storhvalen - Slaattelid, Aasmund (Aschehoug, 1938)
Keywords: Sørishavet; fangst; hvalfangere; hvalfangst; pelagisk; sjøfolk

Biochemical studies of whaling problems : 1 - Valsø, Jakob; Pedersen, Torbjørn (I kommisjon hos Dybwad, 1938)
Inneholder: Jakob Valsø: The Hypophysis of the Blue Whale. (Balaenoptera musculus L.). Macroscopical and Microscopical Anatomy and Hormone Content. Torbjørn Pedersen: On the Course of Hydrogenation in the Industrial Hardening of Whale Oil with Nickel Formate Catalyst.
Keywords: Sørishavet; biokjemi; biologi; farmakologi; hvaler; hvalfangst; hvalolje; pelagisk

Sydishavet - Balleny öyene (Blad 3) (Hvalfangernes Assuranceforening, 1937)
Keywords: Norvegia ekspedisjoner; Sørishavet; geografi; kartlegging

Sydishavet - Hearst Land, Charcot ö (Blad 4) (Hvalfangernes Assuranceforening, 1937)
Keywords: Norvegia ekspedisjoner; Peter I. Øy; Sørishavet; geografi; kartlegging

Sydishavet - Kong Haakon VII Hav (Blad 1) (Hvalfangernes Assuranceforening, 1937)
Keywords: Bouvetøya; Norvegia ekspedisjonene; Sørishavet; Thorshammer ekspedisjon; geografi; kartlegging

Sydishavet - Kronprins Olav Land (Blad 2) (Hvalfangernes Assuranceforening, 1937)
Keywords: Lars Christensen; Norvegia ekspedisjonene; Sørishavet; Thorshavn ekspedisjon; geografi; kartlegging

Sydishavet (Blad 6) - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1937)
Keywords: Sørishavet; geografi; kartlegging

Sydishavet (Blad 7) - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1937)
Keywords: Sørishavet; geografi; kartlegging

Sydishavet (Blad 8) - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1937)
Keywords: Sørishavet; geografi; kartlegging

The Story of Whaling - Hjort, Johan (The Scientific Monthly, 1937)
Keywords: Sørishavet; historie; hvalfangst

Pelagic whaling in the Antarctic : 6 : The season 1935-1936 - Hjort, Johan; Lie, J; Ruud, Johan T (I kommisjon hos Dybwad, 1937)
Keywords: Sørishavet; hvaler; hvalfangst; pelagisk; polarområdene

Antarktis og Sydishavet (Norwegian Mapping Authority / Kartverket, 1936)
Keywords: Antarktis; Jason ekspedisjonene; Norvegia ekspedisjoner; Odd I; Sørishavet; Thorshavn ekspedisjon; ekspedisjonen; geografi; kartlegging

Sydishavet (Blad 1) (Hvalfangernes Assuranceforening, 1936)
Keywords: Bouvetøya; Norvegia ekspedisjonene; Sørishavet; geografi; kartlegging

Omkring hvalfangsten - Bogen, Hans (Samtiden: tidsskrift for politikk, litteratur og samfunnsspørsmål, 1936)
Keywords: Sørishavet; hvalfangst; hvalfangstnæring; hvalolje; pelagisk; økonomi

Tilsjøs under napoleonskrigene : en norsk sjømanns opplevelser 1802-1854 - Eide, Henrik O (Aschehoug, 1936)
Keywords: Sørishavet; biografi; ekspedisjoner; fangst; geografi; historie; sjøfolk; skippere

Hvalfangerregister med opgaver over norsk hvalfangst = Register of the whaling fleet - Hvalfangernes, assuranceforening (Hvalfangernes Assuranceforening = The whalers mutual insurance association, 1936)
Keywords: Sørishavet; hvalfangstflåten; hvalfangstindustri; pelagisk

Antarctic journey (1934-1935) - Næss, Erling Dekke ([E.D. Naess], 1936)
Keywords: S.S.Vikingen; Sørishavet; dagbøker; hvalfangst; hvalfangstindustri; hvalindustri; reisebeskrivelser; reiser; reiseskildringer

Blåhval - Ruud, Johan T (Kvalitet, 1936)
Keywords: Sørishavet; hval; hvalfangst

Bunnen av Weddellhavet (Hvalfangernes Assuranceforening, 1935)
Keywords: Bouvetøya; Norvegia ekspedisjoner; Sørishavet; geografi; kartlegging

Sydishavet (Blad 2) (Hvalfangernes Assuranceforening, 1935)
Keywords: Antarktis; Lars Christensen; Norvegia ekspedisjoner; Sørishavet; Thorshavn ekspedisjon; geografi; kartlegging

Sydishavet - Weddel Havet - Kong Haakon VII hav (Blad 1) (Hvalfangernes Assuranceforening, 1935)
Keywords: Bouvetøya; Norvegia ekspedisjoner; Sørishavet; geografi; kartlegging

Hvalfangsten i Syd-Ishavet : med kart og billeder - Guren, Reidar (Cappelen, 1935)
Keywords: Sørishavet; hvalfangere; hvalfangst; pelagisk

Meteorological observations made on 9 Norwegian whaling floating factories during The International Polar Year 1932-1933 - Harang, Leiv; Hesselberg, Th. (Det norske meteorologiske institutt, 1935)
Keywords: Det internasjonale polaråret; Sørishavet; hvalfangst; meteorologi

Human Activities and the Study of Life in the Sea: An Essay on Methods of Research and Experiment - Hjort, Johan (Geographical Review, 1935)
Keywords: Sørishavet; historie; hvalfangst

Pelagic whaling in the Antarctic : 5 : The season 1934-1935 - Hjort, Johan; Lie, J; Ruud, Johan T (I kommisjon hos Dybwad, 1935)
Keywords: Sørishavet; hvaler; hvalfangst; hvalfangstkonferanse; pelagisk; polarområdene

Hvalbåtliv - Larsen, Fridtjov Barth (Tiden, 1935)
Keywords: Norge; Sørishavet; hvalfangere; hvalfangst; hvalfangstindustri; hvalindustri; norsk; pelagisk

Norges skibsførere : 1933-1935 - Meling, Torjer (red.); Berg, Gabriel (red.); Gausel, Arnold Chr. (red.); Dreyer, Paul (red.) (Dreyer, 1935)
Keywords: Nordmenn; Sørishavet; biografier; historie; hvalfangere; hvalfangst; pelagisk; sjøfolk; skipsfart; skipsførere

Fra »Norvegia« - Ekspedisjonene. Noen meteorologiske og oceanografiske resultater - Mosby, Hakon (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1935)
Keywords: Norvegia ekspedisjoner; Sørishavet; meteorologi; oseanografi; strømmer; vannmasser

Pelagic whaling in the Antarctic : 4 : The season 1933-1934 - Hjort, Johan; Lie, J; Ruud, Johan T; Hansen, Hans Edvard (I kommisjon hos Dybwad, 1934)
Inneholder også: Limits of the pack-ice in the Antarctic in the area between 40° W and 110° E / by H.E. Hansen. S. 39-41, kart.
Keywords: Sørishavet; havis; hvaler; hvalfangst; pelagisk; polarområdene; sjøis

Hvalfangerregister med opgaver over norsk hvalfangst = Register of the whaling fleet - Hvalfangernes, assuranceforening (Hvalfangernes Assuranceforening = The whalers mutual insurance association, 1934)
Keywords: Sørishavet; hvalfangstflåten; hvalfangstindustri; pelagisk

The waters of the Atlantic Antarctic Ocean - Mosby, Håkon (Scientific results of the Norwegian Antarctic expeditions 1927-1928 et sqq. Instituted and financed by consul Lars Christensen : Volume I, 1934)
Keywords: Antarktis; Bouvetøya; Norvegia ekspedisjoner; Sørishavet; hydrografi; oseanografi; strømmer; vannmasser

Wie entsteht die Antarktische Konvergenz? - Sverdrup, Harald Ulrik (Annalen der Hydrographie und Maritimische Meteorologie, 1934)
Keywords: Sørishavet; forskning; havstrømmer; meteorologi; oseanografi

Hval og hvalfangst : utarbeidet efter Hvalrådets skrifter nr. 7 (I kommisjon hos Jacob Dybwad, 1933)
Keywords: Sørishavet; hvaler; hvalfangstindustri; hvalindustri; pelagisk

Sydishavet (Blad 2) (Hvalfangernes Assuranceforening, 1933)
Keywords: Antarktis; Lars Christensen; Norvegia ekspedisjoner; Sørishavet; geografi; kartlegging

Sydishavet (Blad 3) (Hvalfangernes Assuranceforening, 1933)
Keywords: Antarktis; Sørishavet; ekspedisjoner; geografi; kartlegging

Sydishavet - Weddel Havet - Kong Haakon VII hav (Blad 1) (Hvalfangernes Assuranceforening, 1933)
Keywords: Bouvetøya; Norvegia ekspedisjoner; Sørishavet; geografi; kartlegging

Den gamle hvalfangst : kapitler av dens historie - Aagaard, Bjarne (Gyldendal, 1933)
Keywords: Sørishavet; fangst; historie; historikk; hvalfangere; hvalfangst; næringslivet; pelagisk

Linjer i den norske hvalfangsts historie - Bogen, Hans (Aschehoug, 1933)
Keywords: Norge; Sørishavet; fangst; historie; hvalfangere; hvalfangst; pelagisk

Norwegian Pelagic whaling in the Antarctic. 3 : The season 1932-1933 - Hjort, Johan; Lie, J; Ruud, Johan T (I kommisjon hos Dybwad, 1933)
Keywords: Sørishavet; hvaler; hvalfangere; hvalfangst; pelagisk; polarområdene

Essays on population - Hjort, Johan; Ottestad, Per; Klem, Alf; Gunnar, Jahn; Lie, J; Ruud, Johan T (I kommisjon hos Dybwad, 1933)
Contents: Johan Hjort: Whales and Whaling (Introductory Remarks). Per Ottestad: A mathematical method for the study of growth. Alf Klem: On the growth of populations of yeast. Johan Hjort, J. Lie and Johan T. Ruud: The optimum catch. Norwegian pelagic whaling in the Antarctic. 2.
Keywords: Sørishavet; hvaler; pelagisk hvalfangst

Fører med katalog - Hougen, Bjørn ([s.n.], 1933)
Keywords: Antarktis; Sørishavet; historie; hvaler; hvalfangstindustri; hvalindustri; pelagisk

The sea-surface and the air - Mosby, Håkon (Scientific results of the Norwegian Antarctic expeditions 1927-1928 et sqq. Instituted and financed by consul Lars Christensen : Volume I, 1933)
Keywords: Antarktis; Bouvetøya; Norvegia ekspedisjoner; Sørishavet; havoverflaten; hydrografi; meteorologi

Hvalfangsten og storhvalens utryddelse : utdrag av foredrag holdt i Det norske studentersamfund 26.9.1931 - Aagaard, Bjarne (Fram forlag, 1932)
Keywords: Antarktis; Sørishavet; ekspedisjoner; historie; hvalfangere; hvalfangst; politikk

Antarktische und antiboreale Polychaeten nebst einer Hirudinee - Augener, H (Scientific results of the Norwegian Antarctic expeditions 1927-1928 et sqq. Instituted and financed by consul Lars Christensen : Volume I, 1932)
Keywords: Bouvetøya; Norvegia ekspedisjoner; Sørishavet; forskning; havbørsteormer; marin biologi; polychaeter; zoologi

Hvalindustrien : en teknisk-kjemisk undersøkelse : 1 : Råmaterialet - Heyerdahl, Eilif Fredrik (A.W. Brøgger, 1932)
Keywords: Norge; Sørishavet; hvalfangst; hvalfangstindustri; hvalindustri; næringsliv

A Brief History of Whaling - Hjort, Johan (Polar Record, 1932)
Keywords: Sørishavet; historie; hvalfangst

Norwegian Pelagic whaling in the Antarctic. 1 : Whaling grounds in 1929-1930 and 1930-1931 - Hjort, Johan; Lie, J; Ruud, Johan T (I kommisjon hos Dybwad, 1932)
Keywords: Sørishavet; hvaler; hvalfangere; hvalfangst; pelagisk; polarområdene

On the biology of some southern Copepoda - Ottestad, Per (I kommisjon hos Dybwad, 1932)
Keywords: S.S.Vikingen; Sørishavet; Weddellhavet; hoppekreps; hydrografi; krill; marin biologi; plankton

On the biology of southern Euphausiidae - Ruud, Johan Tidemand (Dybwad, 1932)
Keywords: S.S.Vikingen 1929-30; Sørishavet; Weddellhavet; ekspedisjoner; hvalfangst; krill; marin biologi; oseanografi; plankton; zooplankton

Med kokeri og hvalbåt - Steinert, Ragnar (Nasjonalforlaget, 1932)
Keywords: Sørishavet; fangst; hvalfangere; hvalfangst; pelagisk; sjøfolk

Antarktis - Walnum, Ragnv. (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1932)
Keywords: Sørishavet; hvalfangere; isforholdene; isgrenser; iskartet; kart; pakkis

Norvegia-ekspedisjonen 1930-1931 (Norges geografi oppmåling, 1931)
Keywords: Antarktis; Bouvetøya; Norvegia ekspedisjoner; Sørishavet; geografi; kartlegging

Sydishavet - Kong Haakon VII hav (Norges geografi oppmåling, 1931)
Keywords: Antarktis; Sørishavet; ekspedisjoner; geografi; kartlegging

Hvaler og hvalfangst - Hjort, Johan (Fra planteverden og dyreliv, 1931)
Keywords: Sørishavet; historie; hvalbestanden; hvalfangstindustri; pelagisk

Antarctic Research by the Norvegia Expeditions and Others - Holtedahl, Olaf (The Geographical Journal, 1931)
Keywords: Lars Christensen; Norvegia ekspedisjonene; Odd I.; Sørishavet; ekspedisjonen; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; pelagisk; polarområdene

Hvalfangerregister med opgaver over norsk hvalfangst = Register of the whaling fleet - Hvalfangernes, assuranceforening (Hvalfangernes Assuranceforening = The whalers mutual insurance association, 1931)
Keywords: Sørishavet; hvalfangstflåten; hvalfangstindustri; pelagisk

Forgiftningsfaktorer ved katalytisk hydrering av tran - Lund, Jakob (I kommisjon hos Dybwad, 1931)
Keywords: Sørishavet; biokjemi; hvaler; hvalfangst; hvalolje; pelagisk

Bibliografi : antarktisk- og hvalfangstlitteratur - Aagaard, Bjarne (Centraltrykkeriet, 1930)
Keywords: Antarktis; Sørishavet; bibliografi; hvalfangere; hvalfangst

Fangst og forskning i Sydishavet - Aagaard, Bjarne (Gyldendal, 1930)
Keywords: Antarktis; Carl Anton Larsen; Jason (skip); Sørishavet; ekspedisjoner; forskning; historie; hvalfangere; hvalfangst

Skibstyper - Bergh-Smith, Sverre; Jensen, J M (Sjømannsboken : sjøfart, hvalfangst, marine : orientering i sjømannsskap, veiledning til selvstudium, 1930)
Keywords: Sørishavet; hvalfangstindustri; hvalindustri; hvalkokerier; pelagisk; skipsfart; teknologi

Antarctic discoveries - Brown, R N Rudmose (Scottish Geographical Magazine, 1930)
Keywords: Bouvetøya; Norvegia ekspedisjonene; Sørishavet; kartlegging; oppdagelsesreiser

Antarctic and Subantarctic Actiniaria - Carlgren, Oskar (Scientific results of the Norwegian Antarctic expeditions 1927-1928 et sqq. Instituted and financed by consul Lars Christensen : Volume I, 1930)
Keywords: Bouvetøya; Norvegia ekspedisjoner; Sørishavet; forskning; marin biologi; sjøanemoner; sjøroser

Om hval og hvalfangst - Risting, Sigurd (Sjømannsboken : sjøfart, hvalfangst, marine : orientering i sjømannsskap, veiledning til selvstudium, 1930)
Keywords: Sørishavet; historie; hvalfangstindustri; hvalindustri; pelagisk

Mysidacea - Rustad, Ditlef (Scientific results of the Norwegian Antarctic expeditions 1927-1928 et sqq. Instituted and financed by consul Lars Christensen : Volume I, 1930)
Keywords: Norvegia ekspedisjoner; Sørishavet; forskning; krepsdyr; marin biologi; zoologi

Nitrates and Phosphates in the Southern Seas - Ruud, Johan T (ICES Journal of Marine Science, 1930)
Keywords: S.S.Vikingen 1929-30; Sørishavet; Weddellhavet; ekspedisjoner; hval; hvalfangst; krill; marin biologi; oseanografi; plankton; zooplankton

Foran sesongen 1930-1931 : oversikt over norske og utenlandske hvalfangerselskaper, siste fangstsesongs regnskaper - Sveinung, E (E. Sveinung A.S., 1930)
Keywords: Antarktis; Sørishavet; hvalfangstindustri; hvalfangstselskaper; hvalindustri; pelagisk; økonomi

Antarctic whaling and exploration - Aagaard, Bjarne (Scottish Geographical Magazine, 1929)
Keywords: Odd I.; Peter I. Øy; Sørishavet; ekspedisjonen; ekspedisjoner; historie; hval; hvalfangst

Antarctic whaling and exploration - Aagaard, Bjarne (Scottish Geographical Magazine, 1929)
Keywords: Lars Christensen; Norvegia ekspedisjonene; Sørishavet; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; pelagisk; polarområdene

Fangst og forskning i Sydishavet - Aagaard, Bjarne (Hvalfangsten med tilknyttede næringer, 1929)
Keywords: Carl Anton Larsen; Lars Christensen; Norge; Sørishavet; historie; hvalfangere; hvalfangst; pelagisk

[Kart over Antarktika og Sydishavet]. Skisser med "Odd" og "Norvegia" sine ruter i Antarktis 1927-1929 - [Aagaard, Bjarne] (1929)
Keywords: Antarktis; Norvegia ekspedisjoner; Odd I; Sørishavet; ekspedisjonen; geografi; kartlegging

Norske hvalfangstselskaper 1928-1929 - Diesen, Emil (Økonomisk revue, 1929)
Keywords: Antarktis; Sørishavet; hvalfangstindustri; hvalfangstselskaper; hvalindustri; pelagisk; økonomi

Oversikt over norske hvalfangstselskaper - Haller, Geo (Red.) (Hvalfangsten med tilknyttede næringer, 1929)
Keywords: Norge; Sørishavet; hvalfangere; hvalfangst; næringsliv

Efter hval i Sydhavet - Høva, Ernst (Fabritius, 1929)
Keywords: Norge; Sørishavet; ekspedisjoner; historie; hvalfangere; hvalfangst; pelagisk; sjøfolk

Hvalfangerregister med opgaver over norsk hvalfangst = Register of the whaling fleet - Hvalfangernes, assuranceforening (Hvalfangernes Assuranceforening = The whalers mutual insurance association, 1929)
Keywords: Sørishavet; hvalfangstflåten; hvalfangstindustri; pelagisk

Modern Norwegian Whaling in the Antarctic - Isachsen, Gunnar (Geographical Review, 1929)
Keywords: Sørishavet; ekspedisjoner; forskning; historie; hvalfangere; hvalfangstindustri; hvalindustri; pelagisk

Hval og hvalfangst - Risting, Sigurd (Den Norske sjøfarts historie : fra de ældste tider til vore dage, 1929)
Keywords: Norge; Sørishavet; historie; hvalfangere; hvalfangst; hvalfangstindustri; hvalindustri; pelagisk; skipsfart

Om hval og hvalfangst - Risting, Sigurd (Hvalfangsten med tilknyttede næringer, 1929)
Keywords: Norge; Sørishavet; historie; hvalfangere; hvalfangst; næringsliv; pelagisk

Moderne hvalfangst - Sørlle, Petter (Hvalfangsten med tilknyttede næringer, 1929)
Keywords: Norge; Sørishavet; historie; hvalfangere; hvalfangstindustri; pelagisk

Foran sesongen 1929-1930 : oversikt over norske og utenlandske hvalfangerselskaper, siste fangstsesongs regnskaper - Sveinung, E (E. Sveinung A.S., 1929)
Keywords: Sørishavet; hvalfangstindustri; hvalfangstselskaper; hvalindustri; pelagisk; økonomi

James Cook - Haffner, Einar (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1928)
Det er i år 150 år siden James Cook døde. Der er så mange jubileer og minnefester i våre dager at man undertiden synes det kan bli litt for meget av det gode. Men de efterfølgende minneord er helliget en mann som ingen der er geografisk interessert, nogensinde bør glemme.
Keywords: James Cook; Sørishavet; geografi; oppdagelsesreiser; polarekspedisjoner; polarfarere

Hvalfangsten på det frie hav : et fredningsspørsmål historisk og folkerettslig belyst - Ræstad, Arnold (Aschehoug, 1928)
Keywords: Norge; Sørishavet; havrett; hvalfangst; hvalfredningsspørsmål; hvalindustri; internasjonal; pelagisk

Jorden rundt efter blåhvalen - Isachsen, Gunnar (Cappelen, 1927)
Keywords: Norge; Sørishavet; historie; hvalfangere; hvalfangst; hvalfangstindustri; hvalindustri; pelagisk

Hvalfangst i Sydhavet - Mørch-Olsen, Øistein (Tønsbergs Forlag, 1925)
Keywords: Nordmenn; Sørishavet; hvalfangere; hvalfangst; pelagisk

Sydover. Sydfeltene - Risting, Sigurd (Av hvalfangstens historie, 1922)
Keywords: Antarktis; Carl Anton Larsen; Sørishavet; fangst; historie; hvalfangere; hvalfangstindustri; hvalindustri

Aktieselskapet "Ørnen" (Vestfold fylke : Sandefjord ved 75 aars jubilæet 1920, 1920)
Keywords: Christen Christensen; Sørishavet; hvalfangere; hvalfangstindustri; hvalfangstselskaper; hvalindustri; hvalkokeri; næringsliv

Norske skibs- og fangstselskaper 1918. Hvalfangstselskaperne. Supplem. til skibsselskaperne. Dødvegtliste - Diesen, Emil (A/S Økonomisk literatur, 1919)
Keywords: Antarktis; Sørishavet; hvalfangstindustri; hvalfangstselskaper; hvalindustri; næringsliv; pelagisk; økonomi

Norske skibs- og fangstselskaper 1917. Hvalfangstselskaperne. Supplem. til skibsselskaperne. Alfabetisk skibsliste. Dødvegt liste - Diesen, Emil (E. Diesen, 1917)
Keywords: Antarktis; Sørishavet; hvalfangstindustri; hvalfangstselskaper; hvalindustri; næringsliv; pelagisk; økonomi

Norske skibs- og fangstselskaper. Fangstselskaper, rederifortegnelse og supplementer - Diesen, Emil (Brun, 1916)
Keywords: Antarktis; Sørishavet; hvalfangstindustri; hvalfangstselskaper; hvalindustri; næringsliv; pelagisk; økonomi

Om hval og hvalfangst - [Risting, Sigurd] (Joh.s Dahls forl., 1915)
Keywords: Sørishavet; hvalfangstfelter; hvalfangstindustri; hvalindustri; hvalolje; pelagisk

Sandefjord : byens udvikling og nuværende standpunkt - Hoffstad, Olaf Alfred (Hanches bogtrykkeri og forlag, 1914)
Keywords: Norge; Sørishavet; Vestfold; byhistorie; hvalfangere; hvalfangerselskapet; hvalfangstindustri; hvalindustri

Hvalfangsten : dens historie og mænd - Sørensen, G (red.); Hoff, I A (red.); Hoff, J O (red.); Halvorsen, L (red.); Salicath, C (red.) (Norske forlagskompani, 1912)
Keywords: Sørishavet; historie; hvalfangere; hvalfangst; hvalfangstselskaper; pelagisk